Ziegler-Natta catalysts containing electron donor compounds for increasing the molecular weight of polymers
Patent Information
- Application Number
- JP2020564391
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-06-01
- Filing Date
- 2019-05-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-05-29
Smart Images

Figure 0007653259000001 
Figure 0007653259000002 
Figure 0007653259000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 679,263, filed June 1, 2018, which is incorporated by reference in its entirety.
[0002] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to Ziegler-Natta catalysts useful for olefin polymerization. More specifically, embodiments of the present disclosure relate to Ziegler-Natta catalysts for producing ethylene-based polymers having increased molecular weight and high density fractions. [Background technology]
[0003] Polyethylene polymers are one of the most common plastics and can be used in a variety of ways depending on the polymer structure, e.g., bags / liners, caps / closures, sanitary films, industrial injection molding, etc. It is estimated that approximately 80 million tons of ethylene-based polymers are produced each year. The polyethylene industry requires significant and continuous differentiation of polymer products, so researchers have expended considerable effort in searching for process changes that would result in such new products.
[0004] In many polyethylene polymers and copolymers, such as LLDPE, ethylene is typically copolymerized with short-chain olefin comonomers (e.g., 1-butene, 1-hexene, and / or 1-octene). The resulting polyethylene polymer is substantially linear but contains a significant number of short branches, characteristics that give it higher tensile strength, higher impact strength, and higher puncture resistance than low-density polyethylene (LDPE). These improved properties mean that films of lower thickness (gauge) can be made, and the products exhibit improved environmental stress crack resistance. LLDPE is primarily used in film applications due to its toughness, flexibility, and relative transparency. Example products range from agricultural films, food protection wraps, and bubble wrap to multilayer and composite films.
[0005] Ziegler-Natta catalysts have been used for many years to produce a variety of polyethylenes, including LLDPE. These catalysts generally contain a magnesium halide support and at least one transition metal compound, typically a titanium species. Although these catalysts are effective, they generally have limited molecular weight capabilities, especially at high polymerization temperatures. In addition, it is difficult to tailor the composition of polymers made with Ziegler-Natta catalysts. Summary of the Invention
[0006] Thus, there is a continuing need for processes, catalyst compositions, and methods for producing new and different LLDPE polymers. In particular, there is a continuing need for processes, catalyst compositions, and methods for producing ethylene-based polymers having increased weight average molecular weight (Mw), increased high density fraction (HDF), and / or reduced comonomer weight percent. The present disclosure is directed to heterogeneous procatalysts and catalyst systems, and methods and processes utilizing these heterogeneous procatalysts and catalyst systems, for producing ethylene-based polymers having increased Mw and HDF, and reduced comonomer weight percent.
[0007] According to at least one embodiment, the heterogeneous procatalyst comprises a titanium species and at least 100m 2 A preformed magnesium chloride (MgCl2) support having a specific surface area of 100 nm / g and the structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. The heterogeneous procatalyst also includes a chlorinating agent having the structural formula (L): n M(Y) m (XR 2 ) bwherein M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0008] According to at least another embodiment, the heterogeneous procatalyst can include a preformed heterogeneous procatalyst and a metal-ligand complex. The preformed heterogeneous procatalyst can include a titanium species and a MgCl2 support. The metal-ligand complex can be represented by structural formula (L): n M(Y) m (XR 2 ) b where M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is neutral in overall charge. In some embodiments, the catalyst system for olefin polymerization may include a heterogeneous procatalyst and a cocatalyst comprising an organoaluminum compound.
[0009] According to yet another embodiment, a catalyst system for olefin polymerization may include a preformed heterogeneous procatalyst, a metal-ligand complex, and a cocatalyst comprising an organoaluminum compound. The preformed heterogeneous procatalyst may include a titanium species and a MgCl2 support. The metal-ligand complex may be represented by the structural formula (L): n M(Y) m (XR 2 ) b where M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0010] According to yet other embodiments, the process for preparing a heterogeneous procatalyst may include contacting a magnesium chloride component with a chlorinating agent, a titanium species, and a metal-ligand complex. The magnesium chloride component is at least 100 ml. 2 The chlorinating agent may be a preformed MgCl2 support having a specific surface area of 1000 nm / g. The chlorinating agent may have the structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. The metal-ligand complex has the structural formula (L): n M(Y) m (XR 2 ) b where M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0011] According to yet another embodiment, the process for preparing a heterogeneous procatalyst may include contacting components (1) and (2) without further chlorination. Component (1) may be a preformed heterogeneous procatalyst comprising a titanium species and a MgCl2 support. Component (2) may be a compound represented by structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0012] Additional features and advantages are set forth in the following Detailed Description, and in part will be readily apparent to those skilled in the art from that description or will be recognized by practicing the embodiments described herein, including the following Detailed Description, and the claims. It is to be understood that both the foregoing general description and the following detailed description are intended to provide an overview or framework for describing the various embodiments and for understanding the nature and characteristics of the claimed subject matter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether the monomers are of the same or different types. Thus, the generic term polymer encompasses the term "homopolymer," which is commonly used to refer to a polymer prepared from only one type of monomer, and "copolymer," which refers to a polymer prepared from two or more different monomers.
[0014] "Ethylene-based polymer" means a polymer containing more than 50% by weight of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE) containing both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE).
[0015] As used herein, a "solution polymerization reactor" is a vessel in which solution polymerization is carried out, in which ethylene monomer, optionally with comonomer, is dissolved in a non-reactive solvent containing a catalyst and then polymerized or copolymerized. Heat may be removed or added to the solution polymerization reactor and after the reactor, such as by attaching the reactor to one or more heat exchangers. High reactor temperatures may be necessary to keep the polymer in a liquid state. Hydrogen may be utilized in solution polymerization processes, but is not required in all solution polymerization processes.
[0016] Ziegler-Natta catalysts are commonly used to produce ethylene-based polymers in copolymerization processes for copolymerizing ethylene and one or more alpha-olefin comonomers. In these copolymerization processes carried out with typical Ziegler-Natta catalysts, the average molecular weight of the polymer decreases rapidly as the polymerization temperature is increased. However, higher polymerization temperatures in solution polymerization processes increase production throughput and produce ethylene-based polymers with desirable polymer properties such as excellent optics and dart / tear balance. Increasing the molecular weight capability of the Ziegler-Natta catalyst can expand the ability to make new products and can enable polymerization at higher polymerization temperatures.
[0017] The present disclosure is directed to heterogeneous procatalysts and catalyst systems of the Ziegler-Natta type that exhibit increased molecular weight capabilities. The catalyst systems disclosed herein may include a heterogeneous procatalyst and a cocatalyst. The heterogeneous procatalyst may include a titanium species, a preformed magnesium chloride (MgCl2) support, a chlorinating agent, and a donor compound. The donor compound may be represented by the structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation, each L is a neutral ligand or (=O), and Y is a halide or (C-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0 (zero), 1, or 2, m is 0 (zero), 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6. The metal-ligand complex may be overall neutral in charge. The preformed MgCl2 support has a specific surface area (m 2 / g). The metal-ligand complex donor compound may be incorporated into the heterogeneous procatalyst or may be added to a preformed heterogeneous procatalyst to modify the preformed heterogeneous procatalyst to produce the heterogeneous procatalyst. In some embodiments, the metal-ligand complex may be incorporated into the catalyst system as an external donor such that the catalyst system comprises a preformed heterogeneous procatalyst, a cocatalyst, and a metal-ligand complex.
[0018] Also disclosed is a polymerization process that includes contacting ethylene and optionally one or more α-olefin comonomers with a catalyst system comprising a heterogeneous procatalyst and optionally a cocatalyst according to embodiments disclosed herein to form an ethylene-based polymer. The ethylene-based polymer produced in the presence of the catalyst systems disclosed herein can exhibit increased molecular weight, increased high density fraction, and reduced content of optional comonomers.
[0019] In some embodiments, the process for producing a heterogeneous procatalyst may include preparing a preformed MgCl2 support, contacting the MgCl2 support with a chlorinating agent to condition the MgCl2 support, contacting the prepared MgCl2 support with titanium species, and contacting a slurry containing the prepared MgCl2 support and titanium species with a donor compound. The preformed MgCl2 support may be a reaction product of a solution of an alkyl magnesium compound in a hydrocarbon diluent and a chloride source. In some embodiments, the hydrocarbon diluent is not separated from the MgCl2 support. In other embodiments, the hydrocarbon diluent may be separated from the MgCl2 support. The preparation of the preformed MgCl2 support may include reacting an organomagnesium compound or a complex containing an organomagnesium compound with a chloride compound, such as a metal or nonmetal chloride, under conditions suitable for making the preformed MgCl2 support, as described herein below. Examples of organomagnesium compounds and / or complexes can include, but are not limited to, magnesium C2-C8 alkyls and aryls, magnesium alkoxides and aryloxides, carboxylated magnesium alkoxides, and carboxylated magnesium aryloxides, or combinations thereof. In some embodiments, the organomagnesium compounds can include magnesium C2-C8 alkyls, magnesium C1-C8 alkoxides, or combinations thereof. In some embodiments, the organomagnesium compounds can be alkylmagnesium compounds, such as butylethylmagnesium.
[0020] The organomagnesium compound or complex may be soluble in a hydrocarbon diluent, such as an inert hydrocarbon diluent. Examples of hydrocarbon diluents may include, but are not limited to, liquefied ethane, propane, isobutane, n-butane, n-hexane, various isomeric hexanes, isooctane, paraffinic mixtures of alkanes having 5 to 20 carbon atoms, industrial solvents composed of saturated or aromatic hydrocarbons, such as cyclohexane, methylcyclopentane, dimethylcyclohexane, dodecane, kerosene, naphtha, and combinations thereof. In some embodiments, the hydrocarbon diluent may be substantially free of olefinic compounds and other impurities. As used herein, the term "substantially free" of a component means that the composition contains less than 0.1% by weight of a component (e.g., impurity, compound, element, etc.). In some embodiments, the hydrocarbon diluent may have a boiling point in the range of about -50°C to about 200°C. In some embodiments, the hydrocarbon diluent may include an isoparaffinic solvent. Examples of isoparaffinic solvents can include, but are not limited to, ISOPAR™ synthetic paraffinic solvents available from ExxonMobile (e.g., ISOPAR™ E paraffinic solvents), and special boiling point (SBP) solvents available from Shell Chemicals (e.g., SBP 100 / 140 high purity dearomatized hydrocarbon solvents). Other examples of hydrocarbon diluents can include ethylbenzene, cumene, decalin, and combinations thereof.
[0021] In some embodiments, the process of preparing the preformed MgCl2 support may include dispersing an organomagnesium compound in a hydrocarbon diluent to form a solution or slurry. The concentration of the organomagnesium compound in the hydrocarbon diluent may be sufficient such that when the chloride compound and the organomagnesium compound are combined, the resulting slurry may contain a sufficient concentration of the organomagnesium compound to provide efficient production of the MgCl2 support without the use of an excessive amount of hydrocarbon diluent. The concentration of the organomagnesium compound should not be so high that the slurry cannot be adequately mixed / agitated or fluidly transported during and after the synthesis. The solution or slurry of the organomagnesium compound dispersed in the hydrocarbon diluent may be contacted with a chloride compound to produce the MgCl2 support. The chloride compound may be a chloride of a metal or nonmetal. For example, in some embodiments, the chloride compound may be hydrogen chloride gas. In some embodiments, the solution or slurry of the organomagnesium compound and the chloride compound may be contacted at a temperature between -25°C and 100°C, or between 0°C and 50°C. In some embodiments, the solution or slurry of the organomagnesium compound and the metal or non-metal chloride may be contacted for a period of from 1 hour to 12 hours, or from 4 hours to 6 hours.
[0022] The reaction of the chloride compound with the organomagesium compound can produce a preformed MgCl2 support, which can be a MgCl2 slurry containing MgCl2 particles dispersed in a hydrocarbon diluent. In some embodiments, the MgCl2 slurry can have a concentration of MgCl2 between 0.05 mol / L and 10.0 mol / L, or about 0.2 mol / L. The preformed MgCl2 support can have a concentration of at least 100 m 2 For example, in some embodiments, the preformed MgCl support may have a specific surface area of 100 m 2 ~1000m 2 / g, 200m 2 / g~800m 2 / g, or 300m 2 / g~700m 2 / g of average surface area.
[0023] In some embodiments, the preformed MgCl support may be further processed by heat treating the preformed MgCl support at a temperature of at least 100° C. for at least 30 minutes to produce a heat treated MgCl support dispersed in a hydrocarbon diluent. For example, in some embodiments, a preformed MgCl support comprising MgCl particles dispersed in a hydrocarbon diluent may be heat treated at a temperature of 100° C. or greater, 120° C. or greater, 130° C. or greater, 150° C. or greater, or even 190° C. or greater to produce a preformed MgCl support. In some embodiments, the MgCl2 slurry may be heat treated at temperatures between 100°C-500°C, 100°C-300°C, 100°C-200°C, 120°C-500°C, 120°C-300°C, 120°C-200°C, 130°C-500°C, 130°C-300°C, 130°C-200°C, 150°C-500°C, 150°C-300°C, 150°C-200°C, 190°C-500°C, or 190°C-300°C to produce a heat treated MgCl2 support. In some embodiments, the MgCl2 slurry may be heat treated at two or more different temperatures during heat treatment.
[0024] The preformed MgCl support may be heat treated for a period of 30 minutes (0.5 hours) or more, 1 hour or more, 2 hours or more, 3 hours or more, 6 hours or more, or 10 hours or more to produce a heat treated MgCl support. For example, in some embodiments, the preformed MgCl support may be heat treated for 0.5 h to 240 h, 0.5 h to 120 h, 0.5 h to 48 h, 0.5 h to 24 h, 1 h to 240 h, 1 h to 120 h, 1 h to 48 h, 1 h to 24 h, 2 h to 240 h, 2 h to 120 h, 2 h to 48 h, 2 h to 24 h, 3 h to 240 h, 3 h to 120 h, 3 h to 48 h, 3 h to 24 h, 6 h to 240 h, 6 h to 120 h, 6 h to 48 h, 6 h to 24 h, 10 h to 240 h, 10 h to 120 h, 10 h to 48 h, or 10 h to 24 h to produce a heat treated MgCl support. In some embodiments, when the heat treatment temperature is above 200° C., the treatment time may be reduced to less than 30 minutes, or less than 10 minutes.
[0025] In some embodiments, heat treating the preformed MgCl2 support may include stirring the MgCl2 slurry. Stirring the MgCl2 slurry may be performed simultaneously with heat treating the MgCl2 slurry at a temperature of at least 100° C. for at least 30 minutes. In some embodiments, the MgCl2 slurry may be stirred at a speed of up to 1000 revolutions per minute (rpm), up to 100 rpm, 1 rpm to 1000 rpm, or 1 rpm to 100 rpm. In some embodiments, heat treating the MgCl2 support may include heat treating the MgCl2 in an inert atmosphere. An "inert atmosphere" refers to an atmosphere consisting of compounds and / or gases that do not react with the MgCl2 support or any other components of the heterogeneous procatalyst. For example, heat treating the MgCl2 support may be performed in the presence of an inert gas, such as, for example, nitrogen or argon, that does not react with MgCl2.
[0026] In some embodiments, the heat treated MgCl2 support may be the product of heat treating a preformed MgCl2 support. The heat treated MgCl2 support may include heat treated MgCl2 particles dispersed in a hydrocarbon diluent. Without intending to be bound by theory, it is believed that heat treating the MgCl2 support may alter the surface morphology and surface area of the MgCl2 particles. The resulting changes in the surface morphology and surface area of the MgCl2 resulting from heat treatment may alter the activity of the heterogeneous procatalyst for polymerizing olefins, changing the polymerization behavior of the heterogeneous procatalyst, as well as the molecular weight and composition of the resulting polymer. In some embodiments, after heat treatment, the heat treated MgCl2 support may be heated to 500° C. for 10 min. 2 / g~1000m 2 / g, 200m 2 / g~1000m 2 / g, or 400m 2 / g~1000m 2 In some embodiments, the heat treated MgCl support may have an average surface area of about 400 m 2 / g of average surface area.
[0027] Following preparation of the preformed MgCl support, the preformed MgCl support may be contacted with a chlorinating agent. The chlorinating agent may be represented by the structural formula A(Cl): x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4ーy where A is an element selected from the group consisting of boron, aluminum, gallium, indium, and tellurium; 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. In some embodiments, A can be aluminum. In some embodiments, the chlorinating agent has the structural formula Al(Cl) x (R 1 ) 3ーx or structural formula Si(Cl) y (R 1 )4ーy wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. In some embodiments, the chlorinating agent is aluminum trichloride, methylaluminum dichloride, dimethylaluminum chloride, ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum sesquichloride, isobutylaluminum dichloride, diisobutylaluminum chloride, n-hexylaluminum dichloride, di-n-hexylaluminum chloride, n-octylaluminum dichloride, di-n-octylaluminum chloride, boron trichloride, phenylboron dichloride, dicyclohexylboron chloride, silicon tetrachloride, methyltrichlorosilane, dimethylchlorosilane, chlorotrimethylsilane, ethyltrichlorosilane, dichlorodiethylsilane, methyldichloro ... The chlorinating agent may be selected from ethyl silane, chlorotriethyl silane, n-propyl trichlorosilane, dichlorodi(n-propyl) silane, chlorotri(n-propyl) silane, isopropyl trichlorosilane, dichlorodiisopropyl silane, chlorotriisopropyl silane, n-butyl trichlorosilane, dichlorodi(n-butyl) silane, chlorotri(n-butyl) silane, isobutyl trichlorosilane, dichlorodiisobutyl silane, chlorotriisobutyl silane, cyclopentyl trichlorosilane, dichlorodicyclopentyl silane, n-hexyl trichlorosilane, cyclohexyl trichlorosilane, dichlorodicyclohexyl silane, or combinations thereof. In some embodiments, the chlorinating agent may be selected from ethyl aluminum dichloride, diethyl aluminum chloride, ethyl aluminum sesquichloride, isobutyl aluminum dichloride, and diisobutyl aluminum chloride.
[0028] The preformed MgCl2 support may be contacted with a chlorinating agent under conditions sufficient to condition the preformed MgCl2 support. For example, the preformed MgCl2 support may be contacted with the chlorinating agent at a temperature of 0°C to 50°C, 0°C to 35°C, 25°C to 50°C, or 25°C to 35°C. The preformed MgCl2 support may be contacted with the chlorinating agent at such temperatures for a period of 4 hours to 24 hours, 4 hours to 12 hours, 6 hours to 24 hours, or 6 hours to 12 hours. Without intending to be bound by any theory, it is believed that conditioning the preformed MgCl2 support by contacting the preformed MgCl2 support with a chlorinating agent may facilitate or enhance the adsorption of additional metals, such as titanium species, onto the preformed MgCl2 support. Additionally, the inclusion of a chlorinating agent in the heterogeneous procatalyst may convert any Ti and Mg compounds that are not chlorides to titanium and MgCl2 chlorides. The heterogeneous procatalyst may include a sufficient amount of chlorinating agent to prepare MgCl. In some embodiments, the heterogeneous procatalyst may include an amount of chlorinating agent less than the amount that would result in sufficient excess chloride to chlorinate the metal-ligand complex donor compound. In some embodiments, the heterogeneous procatalyst may include a molar ratio of chlorinating agent to MgCl in the heterogeneous procatalyst of 0.05:1 to 2:1, 0.05:1 to 1:1, 0.05:1 to 0.5:1, 0.05:1 to 0.3:1, 0.07:1 to 2:1, 0.07:1 to 1:1, 0.07:1 to 0.5:1, 0.07:1 to 0.3:1, 0.1:1 to 2:1, 0.1:1 to 1:1, 0.1:1 to 0.5:1, or 0.1:1 to 0.3:1.
[0029] The preformed MgCl2 support conditioned with the chlorinating agent may be contacted with a titanium species. The titanium species can be any titanium compound or titanium complex that has catalytic activity when incorporated into the procatalyst and then activated with a cocatalyst. For example, in some embodiments, the titanium species can include titanium halides, titanium alkoxides, or combinations thereof. In some embodiments, the titanium species can be TiCl 4ーc (OR 3 )c or TiCl 3ーd (OR 3 ) d where R 3 But, (C1-C 20 ) hydrocarbyl, c is 0, 1, 2, 3, or 4, and d is 0, 1, 2, or 3. For example, in some embodiments, titanium species may include, but are not limited to, titanium(IV) tetrachloride (TiCl4), titanium(III) trichloride (TiCl3), diethoxytitanium(IV) dichloride (TiCl2(OC2H5)2), diisopropoxytitanium(IV) dichloride ((TiCl2(O-i-C3H7)2), di-n-butoxytitanium(IV) dichloride (TiCl2(O-n-C4H9)2), diisobutoxytitanium(IV) dichloride (TiCl2(O-i-C4H9)2), triisopropoxytitanium(IV) chloride (TiCl(O-i-C3H7)3), tri-n-butoxytitanium(IV) chloride (TiCl(O-n-C4H9)3), triisobutoxytitanium(IV) chloride (TiCl(O-i-C4H9)3), titanium(IV) tetraisopropoxide (Ti(O i Titanium(IV) ethoxide (Ti(OC2H5)4), titanium(IV) n-butoxide (Ti(O-n-C4H9)4), titanium(IV) isobutoxide (Ti(O-i-C4H9)4), titanium(IV) 2-ethylhexoxide (Ti(OCH2CH(C2H5)(C4H9))4), dichlorobis(2,2,6,6-tetramethyl-3,5-heptanedionato)titanium(IV), tris(2,2,6,6-tetramethyl-3,5-heptanedionato)titanium(III), tetrachlorobis(tetrahydrofuran)titanium(IV), trichlorotris(tetrahydrofuran)titanium(III), methyltitanium(IV) trichloride, or combinations thereof. In some embodiments, the titanium species is titanium(IV) tetrachloride or titanium(IV) tetraisopropoxide (Ti(O i Pr) 4).
[0030] The preformed MgCl2 support prepared with the chlorinating agent may be contacted with titanium species under conditions sufficient to form a slurry in which at least a portion of the titanium species are adsorbed onto the preformed MgCl2 support. For example, in some embodiments, the preformed MgCl2 support prepared with the chlorinating agent may be contacted with titanium species at a temperature of 0° C. to 50° C., 0° C. to 35° C., 25° C. to 50° C., or 25° C. to 35° C. In some embodiments, the preformed MgCl2 support prepared with the chlorinating agent may be contacted with titanium species at such temperatures for 1 min to 72 h, 0.5 h to 24 h, 1 h to 12 h, 1 h to 6 h, 3 h to 72 h, 3 h to 24 h, 3 h to 12 h, 6 h to 72 h, 6 h to 24 h, or 6 h to 12 h. In some embodiments, the heterogeneous procatalyst can include a molar ratio of titanium species to MgCl in the heterogeneous procatalyst of 0.005:1 to 0.25:1, 0.005:1 to 0.15:1, 0.005:1 to 0.07:1, 0.01:1 to 0.25:1, 0.01:1 to 0.15:1, 0.01:1 to 0.07:1, 0.05:1 to 0.25:1, 0.05:1 to 0.15:1, or 0.05:1 to 0.07:1.
[0031] Preparing the heterogeneous procatalyst may further include contacting the preformed slurry containing the MgCl2 support, the chlorinating agent, and the titanium species with a donor compound to produce the heterogeneous procatalyst. An electron donor compound refers to an organic molecule that contains a functional group capable of donating a set of two pairs of electrons to an electron acceptor (usually a metal atom). In some embodiments, the donor compound may be a metal-ligand complex. Without intending to be bound by theory, the metal-ligand complex (L) may be a metal-ligand complex. n M(Y) m (XR 2 ) b It is believed that the metal-ligand complex can function like an electron donor molecule due to the lone pair(s) available from the heteroatom(s) in the complex. As mentioned above, the metal-ligand complex can be represented by the structural formula (L): n M(Y) m (XR 2 )b where M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or contains a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0 (zero), 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6. The metal-ligand complex may be neutral in overall charge. In some embodiments, the metal-ligand complex may be soluble in a hydrocarbon solvent, such as the hydrocarbon diluents previously described herein. For example, in some embodiments, the metal-ligand complex may be soluble in the hydrocarbon diluent used to generate the MgCl2 slurry of the preformed MgCl2 support. Without intending to be bound by any theory, it is believed that solubility in the hydrocarbon solvent of the MgCl2 slurry provides better dispersion of the metal-ligand complex in the slurry and promotes interaction between the metal-ligand complex and titanium species on the MgCl2 surface.
[0032] In some embodiments, the metal cation M can be a transition metal cation, including lanthanides and actinides. For example, in some embodiments, M can be selected from cerium, chromium, cobalt, copper, iron, lanthanum, manganese, neodymium, nickel, niobium, samarium, scandium, tantalum, titanium, tungsten, vanadium, yttrium, zinc, or zirconium, in any oxidation state, or combinations thereof. Alternatively, in some embodiments, the metal cation M can be a main group metal cation. Main group metal cations refer to cations including metals / metalloids from groups 1, 2, and 13-16 of the IUPAC periodic table of elements. For example, in some embodiments, the metal cation M can include, but is not limited to, calcium, magnesium, aluminum, gallium, indium, thallium, or tin, in any oxidation state. In some embodiments, M can be selected from vanadium, titanium, chromium, scandium, zirconium, niobium, magnesium, calcium, or combinations thereof.
[0033] In some embodiments, one or more of L can be a neutral ligand. In some embodiments, one or more of L can include a neutral ligand including an oxygen-, nitrogen-, or phosphorus-containing compound, such as ammonia, nitrile, pyridine, amine, phosphine, or combinations thereof. Examples of neutral ligands can include, but are not limited to, ethers, ketones, esters, amines, pyridines, phosphines, phosphites, other neutral ligands, or combinations thereof. In some embodiments, one or more of L can be an oxo group (=O). In some embodiments, X can be oxygen. In some embodiments, X can be a carboxylate group (-OC(=O)-).
[0034] In some embodiments, the metal-ligand complex can be a metal alkoxide or a metal oxyalkoxide. In some embodiments, the metal-ligand complex can be represented by the structural formula M(OR 2 ) ewhere M is a metal cation, e is 2, 3, 4, 5, or 6, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, or a halogenated derivative thereof. In other embodiments, the metal-ligand complex has the structural formula M(=O)(OR 2 ) f where M is a metal cation, f is 1, 2, 3, or 4, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, or a halogenated derivative thereof. In some embodiments, the metal-ligand complex includes vanadium(V) oxytriethoxide, vanadium(V) oxytri-n-propoxide (VO(O n Pr)3), vanadium(V)oxytri-n-butoxide (VO(O n Bu)3), vanadium(V) oxytriisopropoxide (VO(O i Pr)3), titanium(IV) tetraisopropoxide (Ti(O i Pr)4), titanium(IV) ethoxide, diethoxytitanium(IV) dichloride, diisopropoxytitanium(IV) dichloride, di-n-butoxytitanium(IV) dichloride, diisobutoxytitanium(IV) dichloride, triisopropoxytitanium(IV) chloride, tri-n-butoxytitanium(IV) chloride, triisobutoxytitanium(IV) chloride, titanium(IV) tetraisopropoxide (Ti(O i Pr)4), titanium(IV) n-butoxide, titanium(IV) isobutoxide, titanium(IV) 2-ethylhexoxide, niobium(V) n-butoxide, tantalum(V) n-butoxide, scandium(III) isopropoxide, yttrium(III) n-butoxide, lanthanum(III) isopropoxide, samarium(III) isopropoxide, molybdenum(V) ethoxide, iron(III) ethoxide, cerium(IV) isopropoxide, aluminum isopropoxide, or combinations thereof.
[0035] In some embodiments, the metal-ligand complex can be a metal carboxylate or a metal oxycarboxylate. In some embodiments, the metal-ligand complex can be represented by the structural formula M(OC 2 ) g and wherein R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, and g is 2, 3, 4, 5, or 6. In some embodiments, the metal-ligand complex has the structural formula M(=O)(OC(O)R 2 ) h wherein R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, where h is 1, 2, 3, or 4. In some embodiments, the metal-ligand complex can include at least one of titanium(IV) 2-ethylhexanoate, vanadyl acetate, vanadium(IV) oxide stearate, chromium(III) 2-ethylhexanoate, manganese(II) 2-ethylhexanoate, iron 2-ethylhexanoate, cobalt(II) 2-ethylhexanoate, nickel(II) naphthenate, nickel(II) 2-ethylhexanoate, copper(II) 2-ethylhexanoate, copper(II) naphthenate, zinc 2-ethylhexanoate, neodymium(III) 2-ethylhexanoate, neodymium(III) neodecanoate, zirconium(IV) 2-ethylhexanoate, magnesium 2-ethylhexanoate, calcium(II) 2-ethylhexanoate, calcium(II) naphthenate, or combinations thereof. Naphthenates refer to metal salts of naphthenic acid. Naphthenic acid is a mixture of alicyclic carboxylic acids, represented by the formula C n H 2(nーz) O2, where n is 5 to 30 and z is 0 to 4. Naphthenic acids can be isolated from crude oil.
[0036] In some embodiments, for example, after adsorption of the titanium species onto a preformed MgCl2 support, a donor compound, such as the metal-ligand complex described above, may be combined with a slurry containing the preformed MgCl2 support component, titanium species, and chlorinating agent dispersed in a hydrocarbon diluent to produce a heterogeneous procatalyst. In some embodiments, the metal-ligand complex may be combined with the preformed MgCl2 support, titanium species, and chlorinating agent slurry and mixed for a period of 0.5 to 10 minutes, immediately followed by addition of the cocatalyst and carrying out the polymerization reaction. In some embodiments, the metal-ligand complex may be combined with the preformed MgCl2 support, titanium species, and chlorinating agent slurry and mixed for a period of more than 10 minutes, immediately followed by addition of the cocatalyst and carrying out the polymerization reaction. The heterogeneous procatalyst can have a molar ratio of metal-ligand complex (i.e., donor compound) to titanium species in the heterogeneous procatalyst of 0.1:1 to 10:1, 0.5:1 to 5:1, 1:1 to 1:3, 1:1 to 1:2.5, 1:1 to 1:2, 1:1.5 to 1:3, 1:1.5 to 1:2.5, 1:1.5 to 1:2, or 1:2 to 1:3.
[0037] In some embodiments, the heterogeneous procatalyst may optionally include one or more second transition metals, with at least a portion of the second metals being adsorbed onto the preformed MgCl2 support to produce a multimetallic heterogeneous procatalyst. The second transition metals may be independently selected from zirconium, hafnium, vanadium, scandium, niobium, tantalum, chromium, molybdenum, and tungsten. In some embodiments, the second transition metals may be independently selected from zirconium, hafnium, vanadium, and chromium. These second transition metals may be incorporated into the heterogeneous procatalyst in any of a variety of manners known to those skilled in the art, but generally, contact between the preformed MgCl2 support containing titanium species and the selected second transition metal(s) in a liquid phase, such as, for example, a suitable hydrocarbon diluent, may be suitable to ensure deposition of the second transition metal(s) to form the multimetallic heterogeneous procatalyst. In some embodiments, the second transition metal may be incorporated into the heterogeneous procatalyst prior to the metal-ligand complex.
[0038] Without intending to be bound by theory, it is believed that the excess of the chlorinating agent Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y In the presence of structural formula (L) n M(Y) m (XR 2 ) b A portion of the metal-ligand complex having the formula TiCl may be chlorinated and lose its effectiveness as an electron donor. 4ーc (OR 3 ) c or TiCl 3ーd (OR 3 ) d In some embodiments, the chlorinating agent (Al(Cl) x (R 1 ) 3-x and / or Si(Cl) y (R 1 ) 4-y) vs. OR in the heterogeneous procatalyst 3 and XR 2 The total amount of (e.g., OR 3 and XR 2 The molar ratio of the total of (a) to (b) is 0.33 to 1.45, 0.40 to 1.14, or 0.50 to 0.94.
[0039] In some embodiments, when the metal-ligand complex is a metal alkoxide, metal oxyalkoxide, metal carboxylate, metal oxycarboxylate, or halogenated derivatives of these compounds, and the metal-ligand complex is the same as the Ti species or the second transition metal, the metal-ligand complex may be added to a preformed procatalyst containing the same Ti compound or the same compound of the second transition metal. For example, Ti(O i When Ti(OPr)4 is used as the Ti species in the preformed heterogeneous procatalyst and also as the metal-ligand complex, Ti(OPr)4 as the metal-ligand complex donor is used. i Pr)4 as Ti species and Ti(O i In another embodiment, VO(OPr)4 may be added to a preformed heterogeneous procatalyst produced using VO(O n When VO(OPr)3 is used as the second transition metal and as the metal-ligand complex donor, n Pr)3 as the second transition metal and VO(O n The catalyst may be added to a preformed heterogeneous procatalyst made using Pr).
[0040] As previously mentioned, in some embodiments, the heterogeneous procatalyst may include a preformed heterogeneous procatalyst and a metal-ligand complex. As used in this disclosure, the term "preformed heterogeneous procatalyst" refers to an existing functional Ziegler-Natta procatalyst composition that has already been determined to have catalytic activity for catalyzing polymerization and copolymerization reactions, and copolymerization reactions that become active when combined with a cocatalyst. In some embodiments, the preformed heterogeneous procatalyst may include at least a titanium species and a MgCl2 support. For example, in some embodiments, the titanium species may be titanium tetrachloride (TiCl4), such that the preformed heterogeneous procatalyst includes TiCl4 and a MgCl2 support. In some embodiments, the preformed heterogeneous procatalyst may include Ti(O i The titanium species was titanium tetraisopropoxide (Ti(OPr)4) and MgCl2 support. i Pr)4). Ti(O i It is understood that at least a portion of Pr) can be converted to Ti chloride(s) upon chlorination with a chlorinating agent. In some embodiments, the preformed heterogeneous procatalyst can include any commercially available Ziegler-Natta procatalyst that includes at least TiCl and a MgCl support and becomes active when combined with a cocatalyst.
[0041] The heterogeneous procatalyst can be prepared by contacting a metal-ligand complex with a preformed heterogeneous procatalyst. For example, in some embodiments, a process for preparing a heterogeneous procatalyst can include providing a preformed heterogeneous procatalyst comprising a titanium species and a MgCl2 support. The process can further include contacting the preformed heterogeneous procatalyst with the metal-ligand complex without further chlorination. Without intending to be bound by theory, it is believed that further chlorination may convert the metal-ligand complex to a chloride compound(s), thus reducing its effectiveness as an electron donor.
[0042] In some embodiments, the heterogeneous procatalyst may include a preformed heterogeneous procatalyst and a metal-ligand complex, where the preformed heterogeneous procatalyst includes a titanium species (such as titanium tetrachloride) and a MgCl2 support. In these embodiments, the preformed heterogeneous procatalyst may be modified by adding the metal-ligand complex to the preformed heterogeneous procatalyst to produce a heterogeneous procatalyst of the present disclosure that is capable of producing ethylene-based polymers with higher Mw and high density fractions, as well as reduced comonomer weight percent. Contacting the preformed heterogeneous procatalyst with the metal-ligand complex may be carried out under a wide variety of conditions. Such conditions may include, for example, contacting the preformed heterogeneous procatalyst with the metal-ligand complex under an inert atmosphere, such as nitrogen, argon, or other inert gas, at temperatures between 0° C. and 100° C., 0° C. and 80° C., 15° C. and 80° C., 15° C. and 60° C., 15° C. and 50° C., or 20° C. and 50° C. After contacting, it is not necessary to separate the hydrocarbon soluble component from the hydrocarbon insoluble component. The contact time between the preformed heterogeneous procatalyst and the metal-ligand complex prior to contacting with the cocatalyst to form the catalyst system can be 10 minutes or more, 0.5 hours or more, 1 hour or more, 24 hours or more, 168 hours or more, or 700 hours or more. It is believed that the effects of the metal-ligand complex may change slightly or slowly over time. However, these effects remain over long periods of time. The molar ratio of the metal-ligand complex (i.e., donor compound) to the titanium species in the preformed heterogeneous procatalyst can be 0.1:1 to 10:1, 0.5:1 to 5:1, 1:1 to 1:3, 1:1 to 1:2.5, 1:1 to 1:2, 1:1.5 to 1:3, 1:1.5 to 1:2.5, 1:1.5 to 1:2, or 1:2 to 1:3.
[0043] The heterogeneous procatalyst can be activated by contacting the heterogeneous procatalyst with a cocatalyst. The cocatalyst can include at least one organometallic compound, such as an alkyl or haloalkyl of aluminum, an aluminoxane, an alkylaluminum alkoxide, an alkylaluminum halide, a Grignard reagent, an alkali metal aluminum hydride, a metal alkyl, an alkali metal borohydride, an alkali metal hydride, an alkaline earth metal hydride, or the like. In some embodiments, the cocatalyst can be an organoaluminum compound. In some embodiments, the cocatalyst can be selected from an alkylaluminum, a haloalkylaluminum, an alkylaluminum halide, and mixtures thereof. In some embodiments, the cocatalyst can be selected from triethylaluminum, trimethylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum chloride, methylaluminoxane (MAO), modified methylaluminoxane (MMAO), diethylaluminum ethoxide, and mixtures thereof. As previously mentioned, the catalyst system can include a heterogeneous procatalyst and a cocatalyst. Preparing the catalyst system can include contacting the heterogeneous procatalyst with a cocatalyst.
[0044] Formation of the catalyst system from the reaction of the heterogeneous procatalyst and the cocatalyst may be carried out in situ (in place) just prior to loading into the polymerization reactor or prior to polymerization. Thus, contacting the heterogeneous procatalyst with the cocatalyst (or preformed heterogeneous procatalyst, metal-ligand complex, and cocatalyst) to prepare the catalyst system may be carried out under a wide variety of conditions. Such conditions may include, for example, contacting the heterogeneous procatalyst with the cocatalyst at temperatures between 0° C. and 250° C., between 0° C. and 200° C., between 15° C. and 250° C., between 15° C. and 200° C., between 15° C. and 50° C., or between 150° C. and 250° C. under an inert atmosphere such as nitrogen, argon, or other inert gas. Preparation of the catalytic reaction product (i.e., the catalyst system) does not require separation of the hydrocarbon-soluble component from the hydrocarbon-insoluble component. The contact time between the heterogeneous procatalyst and the cocatalyst prior to the polymerization reaction can be from greater than 0 minutes to 10 days, greater than 0 minutes to 60 minutes, greater than 0 minutes to 5 minutes, 0.1 minutes to 5 minutes, 0.1 minutes to 2 minutes, or 1 minute to 24 hours. Various combinations of these conditions may be used. In some embodiments, the catalyst system can have a molar ratio of the cocatalyst to the titanium species in the heterogeneous procatalyst of 0.5:1 to 50:1, 3:1 to 20:1, 3:1 to 15:1, 3:1 to 10:1, 3:1 to 8:1, 5:1 to 20:1, 5:1 to 15:1, 5:1 to 10:1, 8:1 to 20:1, or 8:1 to 15:1.
[0045] In some embodiments, the metal-ligand complex may be used as an external donor compound instead of being incorporated into the heterogeneous procatalyst. For example, in some embodiments, the catalyst system may include a preformed heterogeneous procatalyst, a metal-ligand complex, and a cocatalyst as described hereinabove. The catalyst system may be prepared by contacting the preformed heterogeneous procatalyst, the metal-ligand complex, and the cocatalyst. For example, when a metal-ligand complex is used as the external donor compound, the metal-ligand complex may be combined with the preformed heterogeneous procatalyst and the cocatalyst immediately prior to introducing the catalyst system into the polymerization reactor system. In some embodiments, the preformed heterogeneous procatalyst, the metal-ligand complex, and the cocatalyst as described hereinabove may be added simultaneously and separately to the reactor. In these embodiments, the contact between the preformed heterogeneous procatalyst and the metal-ligand complex occurs within the polymerization reactor.
[0046] Once the catalyst system comprising the heterogeneous procatalyst and the cocatalyst is prepared, the catalyst system can be used in a polymerization or copolymerization process to polymerize olefins. For example, in some embodiments, the catalyst system can be utilized in a polymerization or copolymerization process to make ethylene-based polymers such as linear low density polyethylene (LLDPE) and other ethylene-based polymers. In some embodiments, the polymerization or copolymerization process can include contacting ethylene and optionally one or more α-olefin comonomers with the catalyst system comprising the heterogeneous procatalyst and optionally a cocatalyst to form an ethylene-based polymer. The olefin polymerization / copolymerization reaction may be carried out in a reaction medium. The reaction medium can be a hydrocarbon diluent such as an isoparaffin, an aliphatic hydrocarbon, or any of the other hydrocarbon diluents previously described in this disclosure. The olefin polymerization / copolymerization process can include contacting an olefin or a combination of olefins with the reaction medium in the presence of a catalyst system comprising a heterogeneous procatalyst, or a preformed heterogeneous procatalyst, and a metal-ligand complex, and a cocatalyst. The conditions may be any suitable, for example a molecular weight regulator such as hydrogen may also be present in the reaction vessel to inhibit the formation of undesirable high molecular weight polymers.
[0047] Any ethylene polymerization or copolymerization reaction system can be used to produce ethylene-based polymers in the presence of the catalyst system disclosed herein. Such ethylene polymerization or copolymerization reaction systems can include, but are not limited to, slurry phase polymerization processes, solution phase polymerization processes, gas phase polymerization processes, and combinations thereof. The polymerization or copolymerization process can be carried out in one or more conventional reactors, examples of which can include, but are not limited to, loop reactors, stirred tank reactors, fluidized bed reactors, batch reactors, and / or any combinations thereof, in parallel or in series. In some embodiments, the polymerization process can be carried out in two or more reactors in series, parallel, or combinations thereof. In other embodiments, the polymerization process can be carried out in a single reactor. The polymerization process can be a batch polymerization process or a continuous polymerization process. For example, in some embodiments, the polymerization process can be a batch polymerization process that can be carried out in a stirred tank reactor. In some embodiments, the polymerization process can be continuous, such as a polymerization reaction carried out in a continuous solution polymerization reactor. In some embodiments, the polymerization process can be carried out in two continuous solution polymerization reactors in series, where one or more molecular catalysts may be charged in the first reactor and the catalyst system disclosed herein may be charged in the second reactor. In some embodiments, the polymerization process can be carried out in two continuous solution polymerization reactors in series, where the catalyst system disclosed herein may be used in the first reactor and one or more metallocene or molecular catalysts may be used in the second reactor. In some embodiments, the polymerization process can include a reactor in which the catalyst system disclosed herein and one other polymerization catalyst system are present. Other catalyst systems can include any Ziegler-Natta catalyst and any molecular catalyst. The molecular catalyst is a polymerization catalyst system that includes a transition metal complex procatalyst with a well-defined molecular structure, such as a metallocene. In other embodiments, the polymerization process can include two or more polymerization steps. In these embodiments, a catalyst system including a heterogeneous procatalyst disclosed herein can be used in any one or more polymerization steps.
[0048] The polymers produced from the polymerization / copolymerization processes utilizing the catalyst systems disclosed herein are C2-C olefins such as ethylene, propylene, or 4-methyl-1-pentene. 20 In some embodiments, the polymers produced in the presence of a heterogeneous procatalyst can include copolymers of ethylene or propylene with at least one or more alpha-olefin comonomers. In some embodiments, the polymers can include copolymers of ethylene and the above C3-C6 alpha-olefins in combination with other unsaturated comonomers. 20 The ethylene-based polymer may be an ethylene-based polymer, such as a copolymer with at least one of the alpha-olefins. In some embodiments, the comonomer may be an α-olefin comonomer having 20 or fewer carbon atoms. For example, in some embodiments, the α-olefin comonomer may have 3 to 20 carbon atoms, 3 to 10 carbon atoms, or 3 to 8 carbon atoms. Exemplary α-olefin comonomers can include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene. In some embodiments, the ethylene-based polymer may include an α-olefin comonomer selected from the group consisting of 1-butene, 1-hexene, and 1-octene. In some embodiments, the ethylene-based polymer produced in the presence of the catalyst system disclosed herein may be a copolymer of ethylene monomer units and comonomer units selected from 1-butene, 1-hexene, 1-octene, or combinations thereof.
[0049] In the polymerization / copolymerization processes utilizing the catalyst systems described herein, polymerization is effected by adding a catalytic amount of the catalyst system to a polymerization reactor containing the selected α-olefin monomer (e.g., ethylene and / or one or more α-olefin comonomers), or vice versa. The polymerization reactor may be maintained at a temperature of 50° C. to 300° C. For example, in some embodiments, the polymerization reactor may be maintained at a temperature of 50° C. to 230° C., 50° C. to 200° C., 100° C. to 300° C., 100° C. to 230° C., 100° C. to 200° C., or 60° C. to 120° C. In some non-limiting embodiments, the reactants, the catalyst system, or both, may have a residence time in the polymerization reactor of 5 minutes to 4 hours, 5 minutes to 20 minutes, or 0.5 hours to 4 hours. Longer or shorter residence times may alternatively be used. Generally, it is desirable to carry out the polymerization in the absence of moisture and oxygen and in the presence of the catalyst system. The amount of catalyst system can be sufficient to provide the desired productivity (e.g., yield) of the ethylene-based polymer, but not so great that the amount of catalyst system is cost prohibitive, however, it is understood that the most advantageous catalyst concentration will depend on the polymerization conditions, such as temperature, pressure, solvent, and the presence of catalyst poisons.
[0050] In some embodiments, the polymerization / copolymerization process can be carried out at relatively low pressures, such as pressures of 150-3,000 psig (1.0-20.7 MPa), 250-1,000 psig (1.7-6.9 MPa), or 450-800 psig (3.1-5.5 MPa). However, polymerization / copolymerization in the presence of the catalyst systems described herein can be carried out at pressures ranging from atmospheric pressure up to pressures determined by the capabilities (e.g., pressure rating) of the polymerization equipment.
[0051] In some embodiments, the polymerization / copolymerization process may include a support, which may be an inert organic diluent, excess monomer, or both. Oversaturation of the support with polymer can generally be avoided during the polymerization / copolymerization process. If such saturation of the support with polymer occurs before the catalyst system is exhausted, the full efficiency of the catalyst system may not be realized. In some embodiments, the polymerization / copolymerization process may be operated under conditions sufficient to maintain the amount of polymer in the support / diluent at a concentration less than the supersaturated concentration of polymer. For example, in some embodiments, the polymerization / copolymerization process may be operated under conditions sufficient to maintain the amount of polymer in the support / diluent at less than 30 weight percent (wt%) based on the total weight of the reaction mixture. In some embodiments, the polymerization / copolymerization process may include mixing or stirring the reaction mixture to maintain temperature control and improve uniformity of the polymerization reaction throughout the polymerization zone. In some embodiments, including more rapid reaction with a relatively active catalyst, the polymerization / copolymerization process may include refluxing monomer and diluent, if a diluent is included, thereby removing at least a portion of the heat of reaction. In some embodiments, a heat transfer device (eg, a heat exchanger, cooling jacket, or other heat transfer means) may be provided to remove at least a portion of the exothermic heat of polymerization.
[0052] In some embodiments, the reaction mixture added to the polymerization / copolymerization process may include a sufficient amount of ethylene monomer to maintain reactor stability and enhance catalyst efficiency. In some embodiments, the reaction mixture may have a molar ratio of diluent to ethylene monomer of 1:2 to 1:8, 1:2 to 1:5, 1:3 to 1:8, or 1:3 to 1:5. In some embodiments, a portion of the excess ethylene monomer may be vented from the polymerization process to maintain the concentration of ethylene monomer in the reactor.
[0053] In some embodiments, the polymerization / copolymerization process may include contacting hydrogen gas with the reaction mixture during the reaction. The hydrogen gas may be operable to reduce the molecular weight of the ethylene-based polymer as well as to reduce the formation of ultra-high molecular weight molecules of the ethylene-based polymer. In some embodiments, the concentration of hydrogen gas in the reaction mixture may be maintained at 0.001 mole to 1 mole of hydrogen per mole of monomer, including ethylene monomer and any optional alpha-olefin comonomer. Hydrogen may be added to the polymerization reactor along with the monomer stream, as a separate hydrogen feed stream, or both. Hydrogen may be added to the polymerization reactor before, during, and / or after the addition of the monomer to the polymerization reactor. In some embodiments, hydrogen may be added before or during the addition of the catalyst system. In some embodiments, the polymerization / copolymerization process may be carried out without the introduction of hydrogen gas.
[0054] The resulting ethylene-based polymer can be recovered from the polymerization mixture by venting the unreacted monomer, comonomer, diluent, or both. In some embodiments, further removal of impurities may not be necessary. The resulting ethylene-based polymer may contain small amounts of catalyst residues. The resulting polymer may be further melt screened. For example, the ethylene-based polymer may be melted in an extruder and then passed through a plurality of in-line positioned one or more active screens having a micron retention size of 2 μm to about 400 μm. During melt screening, the mass flow rate of the ethylene-based polymer is preferably 5 lb / hr / in. 2 ~about 100lb / hour / in 2 It could be.
[0055] The resulting ethylene-based polymers produced with the catalyst systems disclosed herein may exhibit increased Mw, increased HDF, and reduced weight percent of alpha-olefin comonomer compared to comparative polymers made with otherwise identical comparative procatalysts that do not contain the metal-ligand complex donor compound. The increased molecular weight capability of the heterogeneous procatalysts and catalyst systems disclosed herein may enable the polymerization / copolymerization process to be carried out at higher process temperatures, which may enable the polymerization / copolymerization process to produce ethylene-based polymers with improved properties, such as optical properties and / or dart impact / tear balance, at higher production throughput rates compared to polymers made at lower process temperatures. Additionally, the catalyst systems disclosed herein may be used with molecular catalyst systems for the production of bimodal polymers, where the catalyst systems disclosed herein produce polymer components with high molecular weight and low comonomer content.
[0056] The ethylene-based polymer may comprise less than 50 weight percent of units derived from one or more α-olefin comonomers. All individual values and subranges from less than 50 weight percent are included and disclosed herein. For example, in some embodiments, the ethylene-based polymer may comprise 30 weight percent or less, 20 weight percent or less, 15 weight percent or less, 10 weight percent or less, 8 weight percent or less, 5 weight percent or less, or 3 weight percent or less of units derived from one or more α-olefin comonomers. The ethylene-based polymer may comprise at least 50 weight percent (wt%) of units derived from ethylene. All individual values and subranges from at least 50 to 100 wt% are included and disclosed herein. For example, in some embodiments, the ethylene-based polymer may comprise 70 weight percent to 100 weight%, 80 weight percent to 100 weight%, 85 weight percent to 100 weight%, 90 weight percent to 100 weight%, 95 weight percent to 100 weight%, or even 97 weight percent to 100 weight of units derived from ethylene.
[0057] The ethylene-based polymers produced in the presence of the catalyst systems disclosed herein may further comprise additional components such as other polymers and / or additives. Examples of additives may include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, and combinations thereof. In some embodiments, antioxidants such as IRGAFOS™ 168 and IRGANOX™ 1010 available from Ciba Geigy can be used to protect the ethylene-based polymer composition from thermal and / or oxidative degradation. The ethylene-based polymers may contain any amount of additives. For example, in some embodiments, the ethylene-based polymer can contain from 0.0 wt.% to 10.0 wt.%, from 0.0 wt.% to 7.0 wt.%, from 0.0 wt.% to 5.0 wt.%, from 0.0 wt.% to 3.0 wt.%, from 0.0 wt.% to 2.0 wt.%, from 0.0 wt.% to 1.0 wt.%, or even from 0.0 wt.% to 0.5 wt.% of additives, based on the total weight of the ethylene-based polymer composition including such additives.
[0058] The ethylene-based polymers produced in the presence of the catalyst system disclosed herein may be included in a wide variety of products, including, in certain embodiments, LLDPE, as well as high density polyethylene (HDPE), plastomers, medium density polyethylene, and polypropylene copolymers. For these and other applications, articles may be prepared that exhibit improved overall quality due to the increase in average molecular weight and high density fraction of the ethylene-based polymer. Useful forming operations of the polymer may include, but are not limited to, extrusion and coextrusion of films, sheets, pipes, and fibers, as well as blow molding, injection molding, and rotational molding may be performed. Films may include blown or cast films formed by coextrusion or lamination, and may be useful as shrink films, cling films, stretch films, sealing films, oriented films, snack packaging, heavy duty bags, grocery bags, baked and frozen food packaging, medical packaging, industrial liners, agricultural film applications, and membranes in, for example, food contact and non-food contact applications. Fibers may include melt-spun, solution-spun, and melt-blown fiber operations for use in woven and nonwoven fabric forms to make filters, diaper fabrics, medical garments, and geotextiles. Extruded articles may include medical tubing, wire and cable coatings, geomembranes, and pond liners. Molded articles may include single and multi-layer structures in the form of bottles, tanks, large hollow articles, rigid food containers, and toys.
[0059] Test Method specific surface area The specific surface area of the MgCl2 support was measured by the Brunauer, Emmett, Teller (BET) surface area method. A Tristar 3020 surface area analyzer by Micromeritics was used. To remove the solvent, 30 mL of the MgCl2 slurry was filtered and then reslurried in 30 mL of hexane. The resulting slurry was filtered again under inert atmosphere and washed with additional hexane. This process was repeated once to obtain a filter cake of MgCl2. Residual solvent was removed from the filter cake under vacuum. The filter cake was further dried in a Vac Prep 061 by Micromeritics using a 0.5 inch (1.27 cm) sample tube and a Transeal stopper designed for inert sample protection by loading a 0.2 g sample of vacuum dried MgCl2 into the tube under inert atmosphere with a Transeal stopper. The sample tube was connected to the Vac Prep 061 unit with nitrogen purging. The sample tube was evacuated by opening the Transeal stopper and the evacuated tube was placed in a heating block with an aluminum tube protector. The sample was dried at 110 °C for 3 h under vacuum in the VacPrep061 unit. Nitrogen was then introduced into the sample tube. The dried sample was cooled to room temperature and then the sample tube was removed from the VacPrep061 unit to obtain a fully dried sample. Under an inert atmosphere, 0.1500-0.2000 g of fully dried sample was transferred to a clean sample tube with a tube filler rod. The sample tube was then sealed with a Transeal stopper and connected to a Tristar3020 instrument for surface area measurement. The QUICKSTART method was used for data acquisition.
[0060] density Density is measured in grams per cubic centimeter (g / cc or g / cm 3 ) to report.
[0061] Melt Index Melt index (I2) is measured according to ASTM D1238 at 190°C and 2.16 kg load. Melt flow index (I2) was obtained using a CEAST 7026 or Instron MF20 instrument. The instrument followed ASTM D1238, methods E and N. Melt index (I2) is reported in grams dissolved per 10 minutes (g / 10 min). Melt index I2 was used to characterize the polymer. Generally, a higher I2 value can be correlated with a lower Mw.
[0062] Gel Permeation Chromatography (GPC) The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) coupled to a Precision Detectors (now Agilent Technologies) two-angle laser light scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle was used for measurement purposes. The oven compartment of the autosampler was set to 160°C and the column compartment was set to 150°C. The columns used were three Agilent "Mixed B" 30 cm, 20 micron linear mixed bed columns. The chromatography solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen injected. The injection volume used was 200 microliters (μL) and the flow rate was 1.0 milliliters per minute (mL / min).
[0063] Calibration of the GPC column set was performed with at least 20 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10 intervals between each individual molecular weight. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights equal to or greater than 1,000,000, and 0.05 grams in 50 milliliters of solvent for molecular weights less than 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius (°C) for 30 minutes with gentle agitation. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 1 (EQU.1) (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
number
[0064] A fifth order polynomial was used to fit each polyethylene equivalent calibration point. A small adjustment (approximately 0.415 to 0.44) was made to A to correct for column resolution and band broadening effects, such that the NIST standard NBS1475 is obtained at 52,000 MW.
[0065] Total plate counts for the GPC column set were performed with eicosane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (EQU.2) and symmetry (EQU.3) were measured with a 200 microliter injection according to the following equations:
number
number
[0066] Samples were prepared semi-automatically using the PolymerChar "Instrument Control" software: 2 mg / mL sample target weight was used, and solvent (containing 200 ppm BHT) was added via the PolymerChar high temperature autosampler to a septa-capped vial that had been pre-sparged with nitrogen. Samples were dissolved at 160° C. under "slow" shaking for 2 hours.
[0067] Mn (GPC) , Mw (GPC)、 and Mz (GPC) The calculations were based on the polyethylene equivalent molecular weights obtained from GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph according to the following Equations 4-6 (EQU.4, EQU.5, and EQU.6) using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at equally spaced data collection points (i), and a narrow standard calibration curve at point (i) of Equation 1.
number
[0068] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow rate (Flow (nominal)) of each sample by matching the RV of the respective decane peak in the sample (RV (FM Sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM Calibrated)). Any time change in the decane marker peak is then assumed to be related to a linear shift in the flow rate (Flow (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow marker peak, a least squares fitting routine is used to fit the peaks of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to determine the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (with respect to the narrow standard calibration) is calculated as in Equation 7 (EQU.7). Processing of the flow marker peaks was performed by PolymerChar GPCOne™ software. Acceptable flow correction is such that the effective flow should be within + / - 2% of the nominal flow.
number
[0069] The IR5 detector ratio calibration was performed using 100% NMR spectra of known short chain branching (SCB) frequencies (SCB) ranging from homopolymer (0 SCB / 1000 total C) to approximately 50 SCB / 1000 total C (where total C = carbons in the backbone + carbons in the branches). 13 A series of characterizations was performed using at least ten ethylene-based polymer standards (polyethylene homopolymers and ethylene / octene copolymers) with molecular weights of 100,000 and 100,000 g / mol (measured by C NMR techniques). Each standard had a weight average molecular weight (Mw) between 36,000 g / mol and 126,000 g / mol, as determined by GPC-LALLS. Each standard had a molecular weight distribution (Mw / Mn) between 2.0 and 2.5, as determined by GPC. Examples of polymer properties of the copolymer standards are shown in Table A. [Table 1]
[0070] The "IR5 area ratio" (or "IR5 area ratio") of "baseline-subtracted area response of the IR5 methyl channel sensor" to "baseline-subtracted area response of the IR5 measurement channel sensor" メチルチャネル面積 / IR5 測定チャネル面積 A linear regression of the comonomer weight percent frequency versus the IR5 area ratio was constructed in the form of the following Equation 8 (EQU. 8):
number
[0071] Measurement of HDF (high density fraction) Improved comonomer content distribution (iCCD) analysis was performed using a Crystallization Elution Fractionation instrument (CEF) (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision detector, now Agilent Technologies). A guard column of 20–27 micron glass (MoSCi Corporation, USA) packed in stainless steel, 10 cm (length) × ¼ inch (ID) (0.635 cm ID), was installed just before the IR-5 detector in the detector oven. Orthodichlorobenzene (ODCB, 99% anhydrous grade or technical grade) was used. Silica gel 40 (particle size 0.2–0.5 mm, catalog number 10181-3) was obtained from EMD Chemicals (may be used to dry the ODCB solvent beforehand). The CEF instrument is equipped with an autosampler with N2 purge capability. ODCB is purged with dry nitrogen (N2) for 1 h prior to use. Sample preparation is performed using an autosampler at 4 mg / mL (unless otherwise specified) with shaking at 160 °C for 1 h. Injection volume was 300 μL. The temperature profile of the iCCD was: crystallization from 105 °C to 30 °C at 3 °C / min, thermal equilibration at 30 °C for 2 min (with soluble fraction elution time set at 2 min), elution from 30 °C to 140 °C at 3 °C / min. The flow rate during crystallization is 0.0 ml / min. The flow rate during elution is 0.50 ml / min. Data was collected at one data point / sec.
[0072] For the iCCD column, gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co.) were packed into a 15 cm (length) × 1 / 4 inch (ID) (0.635 cm) stainless steel tube. The column was packed and conditioned using a slurry method according to references (Cong, R; Parrott, A.; Hollis, C.; Cheatham, M. WO2017 / 040127A1). The final pressure of the TCB slurry packing was 150 bar.
[0073] The column temperature calibration was performed using a linear homopolymer polyethylene standard (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M n was performed using a mixture of eicosane (2 mg / mL) in ODCB (approximately 2.6, 1.0 mg / mL) and ODCB (approximately 2.6 mg / mL) in conventional gel permeation chromatography. The iCCD temperature calibration consisted of four steps: (1) calculating the delay volume, defined as the temperature offset, which is the measured peak elution temperature of eicosane minus 30.00 °C; (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data. Here, it is noted that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.; (3) creating a linear calibration line converting elution temperatures ranging from 30.00°C to 140.00°C such that the linear homopolymer polyethylene reference has a peak temperature at 101.0°C and eicosane has a peak temperature of 30.0°C; (4) for the soluble fraction measured isothermally at 30°C, for elution temperatures below 30.0°C, linearly extrapolated by using an elution heating rate of 3°C / min according to references (Cerk and Cong et al., US9,688,795).
[0074] The iCCD comonomer content versus elution temperature was constructed using 12 standards (ethylene homopolymers and ethylene-octene random copolymers made with a single-site metallocene catalyst, with ethylene equivalent average molecular weights ranging from 35,000 to 128,000). All of these standards were analyzed in the same manner as previously specified at 4 mg / mL. Modeling of the reported elution peak temperatures as a function of octene mole % using linear regression yielded a model of Equation 9 (EQU.9) with an R2 of 0.978.
number
[0075] For the entire resin, an integration window is set to integrate all chromatograms with elution temperatures ranging from 23.0°C to 115°C (temperature calibration specified above). The weight percent of the high density fraction (HDF) of the resin is defined by the following Equation 10 (EQU.10):
number
[0076] Catalytic efficiency Catalyst efficiency ("Eff") is calculated based on the amount of ethylene consumed during polymerization per gram of Ti used in the heterogeneous procatalyst (Ethylene(g) / Ti(g)). Grams of Ti refers to grams of Ti attributable to titanium species and does not include Ti attributable to electron donor compounds (metal-ligand complexes). EXAMPLES
[0077] Embodiments of the present disclosure are further clarified by the following examples, which should be understood as being intended to be illustrative in nature and not limiting on the scope of the preceding disclosure or the appended claims.
[0078] Example A: Preparation of preformed procatalyst compositions of Examples 1-12 and Comparative Examples 1-3. In Example A, a preformed procatalyst composition slurry containing magnesium chloride, a chlorinating agent, and titanium species was prepared for use in Examples 1-12 and Comparative Examples 1-3. A 20 wt % solution of n-butylethylmagnesium in heptane was diluted to a concentration of 0.20 M in ISOPAR™ E isoparaffinic solvent from ExxonMobile Corporation as an inert hydrocarbon diluent. Under stirring at 30° C., hydrochloric acid (HCl) was slowly added to the 0.2 M n-butylethylmagnesium solution until the Cl / Mg molar ratio reached 2.04 (Cl mol / Mg mol). The temperature of the reaction mixture was maintained at 30° C.±3° C. throughout the reaction. A magnesium chloride (MgCl2) slurry was obtained without separating the MgCl2 solid from the liquid diluent.
[0079] A solution of 15% ethylaluminum dichloride (EADC) in heptane was slowly added to the MgCl2 slurry with stirring at 30° C. until the EADC / Mg ratio reached 0.3 (EADC mol / Mg mol). The temperature of the reaction mixture was maintained at 30° C.±3° C. during the addition. The mixture was aged at 30° C. for 4 h.
[0080] A solution of 51% titanium(IV) isopropoxide in heptane was then slowly added to the mixture with stirring at 30° C. until the Ti / Mg ratio reached 0.075 (Ti mol / Mg mol). The temperature of the reaction mixture was maintained at 30° C.±3° C. during the addition. The mixture was aged again at 30° C. for at least 8 hours. ISOPAR™ E paraffinic solvent was used to adjust the procatalyst loading concentration. The final Ti concentration of the preformed procatalyst composition of Example A was 0.12 M in the hydrocarbon diluent. The preformed procatalyst composition of Example A had a molar ratio of MgCl2 to EADC to Ti (i.e., MgCl2 / EADC / Ti) of 40 / 12 / 3.
[0081] Comparative Examples 1-3: Batch copolymerization in the presence of a catalyst system that does not contain a metal-ligand complex as the donor compound. In Comparative Examples 1, 2, and 3 (CE1, CE2, CE3), batch reactor copolymerizations of ethylene monomer and 1-octene comonomer were carried out in a 1 gallon stirred reactor using the preformed procatalyst composition of Example A as a comparative procatalyst without a metal-ligand complex as the donor compound. 250 grams (g) of 1-octene (C8) and 1330 g of ISOPAR™ E isoparaffinic solvent (1580 g total including 1-octene comonomer and solvent) were charged to the reactor. The reactor was heated to 190° C. and then saturated with ethylene in the presence of 40 millimoles (mmol) of hydrogen.
[0082] In CE1, no donor compound containing a metal-ligand complex was used. A quantity of the preformed procatalyst composition prepared in Example A and a cocatalyst solution containing triethylaluminum (TEA) were mixed in an overhead shot tank for about 2 minutes and then injected into the reactor. In CE1, a quantity of the preformed procatalyst composition from Example A was added such that the reaction mixture contained a titanium loading of 1.5 micromoles (μmol) of titanium, and a quantity of TEA was added such that the molar ratio of TEA to Ti in the reaction mixture was 10 mol / mol.
[0083] In CE2 and CE3, an amount of the preformed procatalyst composition of Example A was added such that the reaction mixture contained a titanium loading of 4.0 μmol of titanium, and an amount of TEA was added such that the molar ratio of TEA to Ti in the reaction mixture was 15 mol / mol.
[0084] The reactor pressure was maintained at 450 pounds per square inch (psi) (3102.6 kilopascals (kPa), where 1 psi = 6.895 kPa) with ethylene flow to compensate for ethylene consumption during polymerization. After 10 minutes of reaction time, the bottom valve of the reactor was opened and the reactor contents were transferred to a glass kettle. The mixture was then poured into a Mylar dish, cooled, and left in a fume hood overnight to remove most of the solvent via evaporation. The ethylene-based polymers of Comparative Examples 1-3 were then dried in a vacuum oven.
[0085] The comparative catalyst systems CE1-CE3 were evaluated for catalyst efficiency (Cat. Eff.), weight average molecular weight (Mw) of the produced ethylene-based polymer, and comonomer weight percent (C8 wt%) of the produced ethylene-based polymer in accordance with the test methods described herein, and the results are reported below in Tables 1, 2, and 3, respectively.
[0086] Examples 1-3: Batch copolymerization in the presence of a heterogeneous procatalyst containing titanium tetraisopropoxide as the metal-ligand complex donor compound. In Examples 1-3 (E1, E2, and E3), batch reactor copolymerization of ethylene monomer and 1-octene comonomer was carried out using the preformed procatalyst of Example A in the presence of titanium tetraisopropoxide (Ti(O i The reaction was carried out in a one-gallon stirred reactor using a heterogeneous procatalyst prepared by contacting 1-octene with a metal-ligand complex donor compound containing 1,330 g of ISOPAR™ E isoparaffinic solvent (total weight of 1,580 g including 1-octene comonomer and solvent). The reactor was heated to 190° C. and then saturated with ethylene in the presence of 40 mmol of hydrogen.
[0087] Heterogeneous procatalysts were then prepared by contacting the preformed procatalyst composition from Example A with a metal-ligand complex. In Examples 1-3, Ti(O i Pr)4 was used. Ti(O) in ISOPAR™ E isoparaffinic solvent i A solution of Ti(OPr)4 was added to an amount of the preformed procatalyst composition of Example A. The amount of titanium species in each of the preformed procatalysts of Examples 1-3 was compared to the amount of Ti(OPr)4. i The amount of Pr) is provided in Table 1 as the molar ratio of donor / Ti.
[0088] In Examples 1 and 2, Ti(O i The Ti(OPr)4 solution was added to the preformed procatalyst composition of Example A and mixed for about 2 minutes to prepare the heterogeneous procatalyst. The TEA cocatalyst solution was then added to the heterogeneous procatalyst and the contents were mixed for about 2 minutes. The catalyst system comprising the mixture of heterogeneous procatalyst and TEA was then injected into the reactor. In Example 3, Ti(O iA Pr)4 donor compound was added to the preformed procatalyst composition of Example A and the mixture was aged for 24 hours to produce a heterogeneous procatalyst. The Ti loading, the molar ratio of TEA to Ti, and the molar ratio of donor compound to Ti in the preformed procatalyst of Example A in each of the catalyst systems of Examples 1-3 are provided in Table 1. As used throughout the examples, Ti loading refers to the amount of Ti from the titanium species in the preformed procatalyst composition, not including Ti added as a metal-ligand complex electron donor compound. In addition, the molar ratio of TEA to Ti refers to the ratio of TEA to Ti from the titanium species of the preformed heterogeneous procatalyst, not including Ti added as a metal-ligand complex electron donor compound.
[0089] The reactor pressure was maintained at 450 psi (3102.6 kPa) with ethylene flow to compensate for ethylene consumption during copolymerization. After 10 minutes of reaction time, the bottom valve of the reactor was opened and the reactor contents were transferred to a glass kettle. The mixture was then poured into a Mylar dish, cooled, and left in a fume hood overnight to remove most of the solvent via evaporation. The ethylene-based polymer was then dried in a vacuum oven.
[0090] The catalyst systems of Examples 1-3 for producing ethylene-based polymers were evaluated for catalyst efficiency (Cat. Eff.), weight average molecular weight of the ethylene-based polymer produced (Mw by GPC), and comonomer weight percent of the ethylene-based polymer produced (C8 wt % by GPC) according to the test methods described herein, and the results are reported below in Table 1. Δ(Mw) and Δ(C8 wt %) in Table 1 are the change in Mw and C8 wt %, respectively, for each of E1-E3 relative to Comparative Example CE1. [Table 2]
[0091] As shown in Table 1, the metal-ligand complex Ti(O iThe introduction of Ti(OPr)4 as an electron donor into the polymerization reaction resulted in a significant increase of at least 19% in Mw for ethylene-based polymers E1-E3 compared to that of CE1. i The introduction of Pr)4 resulted in a substantial reduction in the comonomer content of at least 18% or more in the ethylene polymers of E1-E3 compared to the polymer of CE1.
[0092] The results in Table 1 also show that increasing the amount of donor in E2 compared to E1 increased the Mw and decreased the comonomer content of the ethylene-based polymers of E2 compared to the ethylene-based polymers of E1. Additionally, the metal-ligand complexes (e.g., Ti(O i E3 can be introduced into the polymerization reaction in a variety of ways. For example, E3 can be introduced into the polymerization reaction as a metal-ligand complex (e.g., Ti(O i This demonstrates that Pr)4) may be incorporated into a heterogeneous procatalyst, aged for a period of time, and then combined with a cocatalyst just prior to the polymerization reaction. The ethylene-based polymers of E3 exhibited higher Mw and lower comonomer content compared to the polymers produced with the comparative catalyst of CE1 and the polymers produced with E1 where the donor compound was contacted with the preformed procatalyst for about 2 minutes.
[0093] Examples 4-8: Batch copolymerization in the presence of a heterogeneous procatalyst containing vanadium oxyisopropoxide as the metal-ligand complex donor compound. In Examples 4 to 8 (E4, E5, E6, E7, and E8), vanadium oxyisopropoxide (VO(O i Pr)3) was used as the metal-ligand complex donor compound in the heterogeneous procatalysis. Related to Examples 1-3, Ti(OPr)3) was used as the metal-ligand complex donor compound. i VO(O) instead of Pr)4 i Using Pr)3, the copolymerization reactions of Examples 4 to 8 were carried out according to the process described above.
[0094] In Examples 4-8, VO(O) in ISOPAR™ E isoparaffinic solvent was used. iA VO(OPr) solution was added to the preformed procatalyst composition of Example A to produce a heterogeneous procatalyst. The amount of titanium species in each of the heterogeneous procatalysts of Examples 4-8 compared to the amount of titanium species in the preformed procatalyst composition of Example A was i The amount of Pr) is provided in Table 2 as the molar ratio of donor / Ti.
[0095] In Examples 4 to 8, VO(O i The Pr)3 solution was added to the preformed procatalyst composition of Example A and mixed for about 2 minutes to form the heterogeneous procatalyst, immediately followed by the addition of the TEA cocatalyst and the catalyst system was injected into the reactor.
[0096] Each of the catalyst systems of Examples 4-8 for producing ethylene-based polymers was evaluated for catalyst efficiency (Cat.Eff.), Mw of the ethylene-based polymer produced, and C8 wt% of the ethylene-based polymer produced according to the test methods described herein. The results of Examples 4-8 and CE2 are reported in Table 2 below. For Example 4, C8 wt% was not determined. The Δ(Mw) and Δ(C8 wt%) in Table 2 are calculated as a comparison of each of Examples 4-8 to CE2. [Table 3]
[0097] As shown by the results in Table 2, VO(O i VO(OPr)3 can also be used as an electron donor compound in the catalyst system to increase the Mw and reduce the comonomer content of the ethylene-based polymers made from the catalyst system. As shown in Table 2, catalyst systems E4-E8 each produced an ethylene-based polymer with a Mw that was at least 5% higher than the Mw of the ethylene-based polymer of CE2. i Catalyst systems E5-E8 having Pr)3 donor compounds also resulted in a reduction in C8 weight percent. Catalyst systems E5-E8 produced ethylene-based polymers exhibiting comonomer weight percents at least 17% lower than the comonomer weight percent of the ethylene-based polymer of CE2.
[0098] VO(O i The VO(OPr)3 donor compound can also increase the catalytic efficiency at low donor / Ti ratios. For example, in E4-E6, the catalytic efficiency is increased by VO(O)3 at donor / Ti ratios below 2.0. i Pr)3, at least 0.50 × 10 6 , which was higher than the efficiency of the catalytic system CE2 without a donor compound. The catalytic efficiency of the catalytic systems E4 to E6 with a donor / Ti ratio of 2.0 or less was also higher than that of the catalytic systems E5 to E6 with the same donor / Ti ratio but without Ti(O) as the donor compound. i The efficiency of the catalytic systems E1 to E3 utilizing Pr4 was substantially higher than that of the catalytic systems E1 to E3 utilizing Pr4 (Table 1).
[0099] Examples 9-12: Batch copolymerization in the presence of a heterogeneous procatalyst containing vanadium oxypropoxide as the metal-ligand complex donor compound. In Examples 9-12 (E9, E10, E11, and E12), vanadium oxypropoxide (VO(O n VO(OPr)3) was used as the metal-ligand complex donor compound in the heterogeneous procatalysis. Related to Examples E4 to E8, VO(OPr)3) was used as the metal-ligand complex donor compound. i VO(O) instead of Pr)3 n Copolymerization reactions for Examples E9-E12 were carried out using VO(OPr)3 in ISOPAR™ E isoparaffinic solvent according to the process previously described. n A VO(OPr)3 solution was added to the preformed procatalyst composition of Example A to produce a heterogeneous procatalyst. The amount of titanium species in each of Examples E9-E12 compared to the amount of titanium species in the heterogeneous procatalyst was n The amount of Pr) is provided in Table 3 as the donor / Ti molar ratio.
[0100] In Examples E9 to E12, VO(O nThe Pr)3 solution was added to the preformed procatalyst composition of Example A and mixed for about 2 minutes to prepare the heterogeneous procatalyst, immediately followed by the addition of the TEA cocatalyst and the catalyst system being injected into the reactor. The catalyst systems E9-E12 for producing ethylene-based polymers were evaluated for catalyst efficiency (Cat. Eff.), Mw of the ethylene-based polymer produced, and C8 wt% of the ethylene-based polymer produced according to the test methods described herein. The results for E9-E12 and CE3 are reported in Table 3 below. The Δ(Mw) and Δ(C8 wt%) in Table 3 are calculated for each of E9-E12 compared to CE3. [Table 4]
[0101] At the same donor / Ti ratio, VO(O i Compared with ethylene-based polymers produced with heterogeneous procatalysts containing VO(OPr)3 (E4–E8 in Table 2), n As shown by the higher increase in Mw and higher reduction in C wt% for the ethylene polymers produced with the heterogeneous procatalysts containing VO(OPr)3 (E9-E12 in Table 3), n Pr)3 is VO(O i VO(O Pr)3 may be a stronger electron donor compound. n VO(OPr)3 donor compounds can also increase the catalytic efficiency at low donor / Ti ratios. For example, at a donor / Ti ratio of 1.0, VO(O n The catalytic efficiency of the E9 catalytic system with Pr is 0.60 × 10 6 , which was substantially higher than the catalytic efficiency of the CE3 catalytic system.
[0102] Comparative Example 4: Sequential copolymerization in the presence of a catalyst system that does not contain a metal-ligand complex donor compound. In Comparative Example 4 (CE4), continuous copolymerization of ethylene-based polymers was carried out in a continuous solution polymerization process using a comparative catalyst system that did not contain a metal-ligand complex donor compound. The continuous solution polymerization process included a reactor that was a liquid-filled, adiabatic, continuous stirred tank reactor (CSTR). The reactor included independent control of all solvent, monomer, comonomer, hydrogen, and catalyst system component feeds. The total feed stream to the reactor, including solvent, monomer, comonomer, and hydrogen, was temperature controlled by passing the total feed stream through a heat exchanger prior to introducing the total feed stream into the reactor. The total feed stream to the reactor was injected into the reactor at one point. The catalyst system components were injected into the polymerization reactor separately from the other feeds. An agitator within the reactor was used to continuously mix the reactants. An oil bath provided additional fine adjustment of the reactor temperature control.
[0103] Ethylene monomer, 1-octene comonomer, and process solvent (SBP100 / 140 by Shell Chemicals) were purified with molecular sieves before being introduced into the reactor. Hydrogen was dried with molecular sieves. The monomer, solvent, and comonomer feed streams were pressurized to a pressure higher than the reaction pressure via mechanical compressors. The monomer, comonomer, solvent, and hydrogen streams were then combined and introduced into the reactor. The individual components of the catalyst system were manually diluted batchwise with purified solvent / diluent and pressurized to a pressure higher than the reaction pressure. The comparative catalyst system for CE4 included the preformed procatalyst composition of Example A and TEA as a cocatalyst. In CE4, no metal-ligand complex donor compound was added to the preformed procatalyst composition of Example A. All reaction feed flow rates were measured with mass flow meters and independently controlled using metering pumps. The reactor conditions for CE4 are provided in Table 4 below.
[0104] The final reactor effluent was sent to a zone where the catalyst system was deactivated by addition and reaction with water. Following catalyst deactivation, the reactor effluent was sent to a devolatilization system where the ethylene-based polymer was removed from the non-polymer stream (e.g., excess monomer or comonomer, solvent, catalyst, etc.). The non-polymer stream was removed from the system and the isolated polymer melt was pelletized and collected. The CE4 comparative catalyst system was evaluated for catalyst efficiency (Cat. Eff.), and the ethylene-based polymers produced in CE4 were evaluated for density, melt index (I2), Mw, and C8 wt% according to the test methods described herein. The results for CE4 are provided in Table 4 below.
[0105] Examples 13 and 14: Sequential copolymerization in the presence of heterogeneous procatalysts containing metal-ligand complex donor compounds. In Examples 13 and 14 (E13 and E14), copolymerization of ethylene-based polymers was carried out in a continuous solution polymerization process using a heterogeneous procatalyst comprising a metal-ligand complex donor compound according to an embodiment of the present disclosure. The ethylene-based polymers of E13 and E14 were made according to the solution polymerization process previously described in CE4. In E13 and E14, the metal-ligand complex of Example A and the preformed procatalyst composition were fed into a static mixer and mixed for about 2 minutes to prepare the heterogeneous procatalyst.
[0106] In E13, the metal-ligand complex is vanadium oxypropoxide (VO(O n In E14, the metal-ligand complex used was titanium isopropoxide (Ti(O Pr)3), the donor / Ti ratio was 2.32, and the TEA / Ti ratio was 8.00. iThe donor / Ti ratio (i.e., the ratio of donor to Ti from the preformed procatalyst composition of Example A) was 1.70, and the TEA / Ti ratio (i.e., the ratio of TEA to Ti from the preformed procatalyst composition of Example A) was 7.82. The process conditions for E13 and E14 are provided in Table 4 below. The catalyst systems of E13 and E14 were evaluated for catalytic efficiency (Cat.Eff.), and the ethylene-based polymers produced with E13 and E14 were evaluated for density, melt index (I2), Mw, and C8 wt% according to the methods described herein. The results are shown in Table 4 below. Δ(Mw) and Δ(C8 wt%) in Table 4 are calculated as a comparison of E13 and E14 to CE4. [Table 5]
[0107] As shown in Table 4, in a continuous solution polymerization reaction under similar reaction conditions, the inclusion of metal-ligand complexes in the heterogeneous procatalyst, such as E13 and E14, produced ethylene-based polymers with higher Mw and lower C8 wt% compared to the ethylene-based polymers produced with the comparative catalyst system, CE4.
[0108] Example B: Preparation of preformed heterogeneous procatalysts containing the heat-treated MgCl2 components of Examples 15-17 and Comparative Example 5. In Example B, a preformed heterogeneous procatalyst incorporating the heat-treated MgCl2 component was synthesized for incorporation into the catalyst systems of Examples 15-18. The MgCl2 component was first generated by synthesizing MgCl2 particles via reacting butylethylmagnesium with hydrochloride gas in ISOPAR™ E isoparaffin solution to generate a 0.20 M MgCl2 slurry. The MgCl2 slurry was stored and handled in a nitrogen-purged glove box to avoid contamination from moisture and oxygen. A 5.9 liter (L) Parr reactor was used to heat-treat the MgCl2 slurry. 2 L of the MgCl2 slurry was charged to the reactor via a transfer vessel designed to be airtight so that the MgCl2 was not exposed to air or moisture. An N2 atmosphere was used to purge and isolate the reactor lines. The reactor was then heated with a heating jacket at 190°C for 1 hour. Heating of the reactor was controlled by a step controller with a ramp time of approximately 1 hour (room temperature to 190°C). After the specified heating time, the reactor was allowed to cool to room temperature in approximately 3 hours. The reactor contents were stirred at 100 rpm during the heating process. Temperature fluctuations were controlled within ±2°C. After the reactor was cooled to room temperature, the slurry containing the heat-treated MgCl2 was transferred back to the glove box with an airtight transfer container to prevent exposure to air and / or moisture.
[0109] The slurry containing the heat-treated MgCl2 was then used to generate the preformed heterogeneous procatalyst of Example B. Ethylaluminum dichloride (EADC, Aldrich, 1.0 M in hexanes) (chlorinating agent), and titanium tetraisopropoxide (Ti(O iThe preformed heterogeneous procatalyst of Example B was produced in a N2-purged glove box according to the following process via the continuous addition of 0.125 M Ti(OPr, Aldrich, 0.125 M in ISOPAR™ E isoparaffinic solvent) (titanium species) to a slurry containing heat-treated MgCl. For the preformed heterogeneous procatalyst of Example B, 10 milliliters (mL) of heat-treated MgCl2 slurry was maintained under constant stirring in a capped glass vial. On day 1, 0.301 mL of 1.0 M EADC solution was added to the heat-treated MgCl2 slurry, and the resulting slurry containing the heat-treated MgCl2 component and EADC was kept stirring overnight. On day 2, 0.603 mL of 0.125 M Ti(OPr, Aldrich, 0.125 M in ISOPAR™ E isoparaffinic solvent) was added to a slurry containing heat-treated MgCl2. i The preformed heterogeneous procatalyst of Example B was prepared by adding EADC to MgCl2 in a molar ratio of 6:40 (i.e., 6 moles of EADC for every 40 moles of MgCl2) and a molar ratio of Ti to MgCl2 of 1.5:40 (i.e., 1.5 moles of Ti(O)2 for every 40 moles of MgCl2). i Pr)4).
[0110] Example C: Preparation of comparative preformed procatalysts containing non-heat treated MgCl2 of Comparative Examples 5-9. The comparative preformed procatalyst of Example C was produced without heat treatment of MgCl. The comparative preformed procatalyst of Example C was produced by first synthesizing MgCl particles via reacting butylethylmagnesium with hydrochloride gas in ISOPAR™ E isoparaffin solution to produce a 0.20 M MgCl slurry. The MgCl slurry was stored and handled in a nitrogen purged glove box to avoid contamination from moisture and oxygen. The MgCl slurry was not heat treated.
[0111] Ethylaluminum dichloride (EADC, Aldrich, 1.0 M in hexane) (chlorinating agent), and titanium tetraisopropoxide (Ti(O iThe comparative preformed heterogeneous procatalyst of Example C was produced in a N purged glove box according to the following process via continuous addition of MgCl slurry (Pr, Aldrich, 0.125 M in ISOPAR™ E isoparaffinic solvent) (titanium species). For the comparative preformed procatalyst of Example C, 10 milliliters (mL) of MgCl slurry (not heat treated) was maintained under constant stirring in a capped glass vial.
[0112] On day 1, 0.600 mL of 1.0 M EADC solution was added to the MgCl2 slurry and the resulting slurry containing the MgCl2 component and EADC was kept stirring overnight. On day 2, 1.199 mL of 0.125 M Ti(O i The EADC to MgCl2 molar ratio was added and the resulting slurry was allowed to continue stirring overnight. On the third day, the comparative preformed procatalyst of Example C was ready for use. The comparative preformed procatalyst of Example C contained a 12:40 EADC to MgCl2 molar ratio (i.e., 12 moles of EADC for every 40 moles of MgCl2) and a 3.0:40 Ti to MgCl2 molar ratio (i.e., 3 moles of Ti(O) for every 40 moles of MgCl2). i Pr)4).
[0113] Examples 15-18: Batch copolymerizations in the presence of a heterogeneous procatalyst generated from the preformed heterogeneous procatalyst of Example B. In Examples 15-17 (E15, E16, and E17), batch copolymerizations of ethylene and 1-octene were carried out in the presence of heterogeneous procatalysts including the preformed heterogeneous procatalyst of Example B with heat treated MgCl2 and metal-ligand complex donor compound. Batch copolymerizations were carried out in a 2 L Parr batch reactor. The reactor was heated by an electric heating mantle and cooled by an internal serpentine cooling coil using water. A dump valve was fitted at the bottom of the reactor to empty the reactor contents into a stainless steel dump pot pre-filled with catalyst deactivation solution (5 mL of a mixture of IRGAFOS® organic phosphite processing stabilizer from BASF, IRGANOX® antioxidant from BASF, and toluene). The dump pot was drained into a blowdown tank under a continuous N2 purge. All solvents used in the copolymerization or catalyst make-up were passed through purification columns to remove impurities. Solvent was passed through two columns, the first containing A2 alumina and the second containing reduced copper on alumina (Q5 reactant). Ethylene was passed through two columns, the first containing A204 alumina and 4 Å molecular sieves and the second containing Q5 reactant. N2 was passed through a single column containing A204 alumina, 4 Å molecular sieves, and Q5 reactant. First, 664 g of ISOPAR™ E solvent and 134 ± 2 g of 1-octene were charged to the reactor from separate tanks and filled to the fill set point of the Ashcroft differential pressure cell. Then, 14.8 ± 0.3 mmol of hydrogen was added after hydrogen solvent addition and the reactor was heated to 190°C. Then, 56 ± 1 g of ethylene was added to the reactor when the reaction temperature reached the reaction pressure (i.e., 475 psi). Further ethylene addition during the polymerization reaction was monitored by a micro-motion flow meter.
[0114] Heterogeneous procatalysts E15-E17 were generated by pipetting the preformed heterogeneous procatalyst of Example B and a solution of the metal-ligand complex in a hydrocarbon diluent into a 5 mL glass vial. The heterogeneous procatalyst of E15 contained 1 molar equivalent of vanadium oxypropoxide (VO(O)) as the metal-ligand complex. nThe heterogeneous procatalyst of E16 contained 2 molar equivalents of (VO(OPr)3) as the metal-ligand complex. n The heterogeneous procatalyst of E17 contained 3 molar equivalents of titanium tetraisopropoxide (Ti(O Pr)3) as the metal-ligand complex. i Pr)4).
[0115] Each heterogeneous procatalyst, E15-E17, was then loaded into a 20 mL syringe with an 18 gauge needle. The vial was rinsed with solvent and the rinse was also loaded into the syringe. The syringe was capped for transport to the batch reactor outside the glove box using a vial sealed with a septum on both ends.
[0116] The cocatalyst solution of TEA in solvent was taken up in a separate syringe. The catalyst system solutions (heterogeneous procatalyst and TEA) were placed in separate syringes and injected within minutes of preparation. The heterogeneous procatalyst was prepared second but injected first, and the TEA solution was rinsed three times (2.5, 2.5, 5 mL).
[0117] The catalyst system components were injected into a shot tank attached to the reactor under N2 flow. The mixture of the two solutions was maintained in the shot tank for 5 minutes, after which the reactor set point was reached, and then introduced into the reactor under a differential pressure of 150 psi. The amounts of metal-ligand complex donor compound and TEA cocatalyst were set based on the amount of Ti present in the preformed heterogeneous procatalyst of Example B (i.e., 1.4 μmol) and are provided in Table 5 below.
[0118] After injection of the catalyst system, the reaction was initiated to produce an ethylene-based polymer. The reaction mixture for analysis was collected in a stainless steel pan for solvent removal. The reactor was washed twice with 850 g of ISOPAR™ E solvent at temperatures between 140° C. and 160° C. The first wash was collected and combined with the reaction mixture. The ethylene-based polymer samples of each example were air-dried overnight to remove most of the solvent and then placed in a vacuum oven under N2 to further remove trapped solvent. The vacuum oven was designed to perform three cycles of 5 minutes of nitrogen flow and vacuum to 40 Torr, ramp to 80° C. at 1° C. / min and hold under vacuum for 3 hours, then ramp to 140° C. and hold for 4 hours. The cooled ethylene-based polymers of E15-E17 were then analyzed for Mw, Melt Index I2, weight percent of high density fraction (HDF wt%), and C8 wt% according to the test methods described herein. The results are shown in Table 5 below.
[0119] Comparative Examples 5 and 6: Batch copolymerization in the presence of preformed heterogeneous procatalysts of Examples C and B. In Comparative Examples 5 and 6 (CE5 and CE6), batch copolymerizations of ethylene and 1-octene were carried out using a preformed procatalyst that did not contain a metal-ligand complex. In CE5, the copolymerization was carried out using the preformed heterogeneous procatalyst of Example B with heat treated MgCl2. In CE6, the copolymerization was carried out using the comparative preformed procatalyst of Example C with non-heat treated MgCl2. The batch copolymerizations of CE5 and CE6 were carried out according to the process previously described in E15-E17. In CE5 and CE6, no metal-ligand complex was added to the preformed procatalyst. Each of the preformed procatalysts of CE5 and CE6 was injected into a shot tank without the addition of a metal-ligand complex as a donor compound. The ethylene-based polymers of CE5 and CE6 were collected and evaluated for Mw, melt index I2, HDF, and C8 wt% according to the test methods described herein. The results are shown in Table 5.
[0120] Comparison of Examples 15 to 17 (E15 to E17) with Comparative Examples 5 and 6 (CE5 and CE6) The compositional parameters of the catalyst systems of E15-17, CE5, and CE6, as well as the Mw, I2, HDF, and C8 wt% of the ethylene-based polymers produced by E15-17, CE5, and CE6 are provided below in Table 5. Δ(Mw), Δ(HDF), and Δ(C8 wt%) in Table 5 are calculated as a comparison between E15-E17 and CE5-CE6, respectively. The Ti loading in the reactor in Table 5 refers to the amount of Ti associated with the preformed procatalyst and does not include the amount of Ti contributed by the electron donor compound. [Table 6]
[0121] Comparison between CE5 and CE6 demonstrates that polymerization in the presence of a preformed procatalyst containing heat-treated MgCl, such as the preformed heterogeneous procatalyst of Example B used in CE5, can produce ethylene-based polymers that exhibit higher Mw, higher HDF, reduced melt index (I2), and reduced comonomer content (C8 wt%) compared to ethylene-based polymers produced in the presence of a comparative preformed procatalyst containing MgCl that has not been heat-treated (e.g., the comparative preformed procatalyst of Example C used in CE6). For example, even when catalyst system CE5 has a lower Ti / Mg molar ratio than catalyst system CE6 (0.0375 vs. 0.075), the ethylene-based polymer of CE5 exhibited a 25% increase in Mw, a 161% increase in HDF, a 43% reduction in I2, and a 28% reduction in C8 wt% compared to the ethylene-based polymer of CE6. For Ziegler-Natta catalysts, catalysts containing lower levels of Ti are typically expected to produce (co)polymers with lower Mw, lower HDF, higher I2, and higher C8 wt%.
[0122] Furthermore, VO(O) was used as a donor compound in heterogeneous procatalysis. nComparison of E15 and E16 to CE5 demonstrates that the inclusion of a VO(OPr)3 metal-ligand complex can increase the Mw and HDF of an ethylene-based polymer and reduce the I2 and C8 wt% compared to an ethylene-based polymer produced with the preformed heterogeneous procatalyst of Example B that does not contain the metal-ligand complex donor compound. n Comparison of E15 to E16 demonstrates that a higher molar ratio of Ti(OPr)3 metal-ligand complex to titanium species (i.e., donor / Ti molar ratio) can further increase the Mw and HDF of the resulting ethylene-based polymer and decrease the I2 and C8 wt%. i The use of a Ti(O)4 metal-ligand complex in combination with heat-treated MgCl2 in a heterogeneous procatalysis also resulted in the addition of Ti(O)4 as a donor compound to a preformed heterogeneous procatalyst. i A comparison of E17 to CE5 demonstrates that it is possible to increase the Mw and HDF and decrease the I2 and C8 wt% of an ethylene-based polymer (E17) compared to an ethylene-based polymer (CE5) produced without the inclusion of a Pr)4 metal-ligand complex.
[0123] Example D: Preparation of a preformed heterogeneous procatalyst containing the heat treated MgCl2 component of Examples 18 and 19. In Example D, a preformed heterogeneous procatalyst incorporating a heat-treated MgCl component was synthesized for incorporation into the catalyst systems of Examples 18 and 19. The preformed heterogeneous procatalyst of Example D was produced according to the process previously described in Example B. The heat-treated MgCl slurry, EADC, and Ti(O i The relative amounts of MgCl, EADC, and Ti(OPr) were calculated using a 40:12:3 molar ratio of heat-treated MgCl to EADC to Ti(OPr) for the heterogeneous procatalyst of Example D. i Pr)4 (i.e., 12 moles of EADC for every 40 moles of MgCl2, and 3.0 moles of Ti(O)4 for every 40 moles of MgCl2. i Pr)4).
[0124] Example E: Preparation of a preformed heterogeneous procatalyst containing the heat treated MgCl2 components of Examples 20 and 21. In Example E, a preformed heterogeneous procatalyst was synthesized incorporating a heat-treated MgCl component for incorporation into the catalyst systems of Examples 20 and 21. The preformed heterogeneous procatalyst of Example E was produced according to the process previously described in Example B. The heat-treated MgCl slurry, EADC, and Ti(O i The relative amounts of MgCl, EADC, and Ti(OPr) were determined for the preformed heterogeneous procatalyst of Example E in a molar ratio of 40:6.8:1.7 for heat-treated MgCl to EADC to Ti(OPr). i 6.8 moles of EADC per 40 moles of MgCl, and 1.7 moles of Ti(O) per 40 moles of MgCl. i Pr)4).
[0125] Examples 18-21: Batch copolymerization in the presence of heterogeneous procatalysts containing metal-ligand complex donor compounds. In Examples 18-21 (E18, E19, E20, and E21), batch copolymerization of ethylene and 1-octene was carried out in the presence of a catalyst system including one of the preformed heterogeneous procatalysts of Examples D or E to which a metal-ligand complex was added as a donor compound. The metal-ligand complex donor compound and the starting preformed heterogeneous procatalyst for each of E18, E19, E20, and E21 are provided in Table 6 below. The molar ratio of the metal-ligand complex to Ti in the preformed heterogeneous procatalyst for the catalyst systems of E18-E21 are also provided in Table 6 below. For E18-E21, the molar ratio of TEA to Ti in the preformed procatalyst was 15:1.
[0126] In E18-E21, copolymerization batches of ethylene and 1-octene were carried out in a 1 gallon stirred reactor charged with 250 g of 1-octene and 1330 g of ISPOAR™ E isoparaffinic solvent (total charge of 1580 g). The reactor was heated to 190° C. and then saturated with ethylene in the presence of 40 mmol of hydrogen. The heterogeneous procatalyst was prepared by adding the metal-ligand complex to the preformed heterogeneous procatalyst of Example D or Example E and mixing for 2 minutes.
[0127] E18 and E20 are titanium tetraisopropoxide (Ti(O i Vanadium oxybutoxide (VO(OPr)4) was used as the metal-ligand complex in E19 and E21. n Bu)3) was used as the metal-ligand complex. The molar ratio of the metal-ligand complex of the catalyst system to Ti from the preformed heterogeneous procatalyst for each of E18-E21 is provided in Table 6 below.
[0128] The heterogeneous procatalyst (containing the metal-ligand complex) and TEA cocatalyst solutions were taken up separately in syringes and injected into the overhead shot tank as previously described in E15-E17. In each example, the catalyst system containing the heterogeneous procatalyst and the TEA cocatalyst were mixed in the shot tank for approximately 2 minutes before being injected into the reactor. The reactor pressure was maintained at 450 psi (3102 kPa) with ethylene flow to compensate for ethylene consumption during polymerization. After 10 minutes of reaction time, the bottom valve of the reactor was opened and the contents were transferred to a glass kettle. The mixture was poured from the glass kettle into a Mylar dish, cooled, and left in a fume hood overnight to remove most of the solvent via evaporation. The resulting ethylene-based polymer was then dried in a vacuum oven.
[0129] Examples 22-23: Batch copolymerization in the presence of the preformed heterogeneous procatalyst of Example C in combination with a metal-ligand complex donor compound. In Examples 22-23 (E22 and E23), batch copolymerization of ethylene and 1-octene was carried out in the presence of a heterogeneous procatalyst containing a metal-ligand complex as the donor compound added to the preformed heterogeneous procatalyst of Example C containing untreated MgCl. In E22, titanium tetraisopropoxide (Ti(O i Vanadium oxybutoxide (VO(OPr)4) was added as a metal-ligand complex in E23. n Bu)3) was added as a metal-ligand complex. The molar ratios of metal-ligand complex to Ti (from preformed heterogeneous procatalyst) for the catalyst systems of E22 and E23 are provided below in Table 6. Copolymerization of E22 and E23 was carried out according to the process previously described for E18-E21.
[0130] Comparative Examples 7 and 8: Batch copolymerization in the presence of preformed heterogeneous procatalysts of Examples D and E without the metal-ligand complex donor compound. In Comparative Examples 7-8 (CE7 and CE8), batch copolymerizations of ethylene and 1-octene were carried out in the presence of a catalyst system including one of the preformed heterogeneous procatalysts of Examples D or E with heat treated MgCl2. The copolymerizations of CE7 and CE8 were carried out without the addition of a metal-ligand complex to the catalyst system. The copolymerization of CE7 was carried out using the preformed heterogeneous procatalyst of Example D, and the copolymerization of CE8 was carried out using the preformed heterogeneous procatalyst of Example E. The copolymerizations of CE7 and CE8 were carried out according to the process previously described in E18-E21, except that no metal-ligand complex was included in the heterogeneous procatalyst.
[0131] Comparative Example 9: Batch copolymerization in the presence of preformed heterogeneous procatalyst of Example C. In Comparative Example 9 (CE9), batch copolymerizations of ethylene and 1-octene were conducted in the presence of a catalyst system that included a comparative preformed procatalyst comprising the preformed procatalyst composition of Example C without the heat treated MgCl2. The copolymerization of CE9 was conducted without the addition of a metal-ligand complex to the procatalyst. The copolymerization of CE9 was conducted according to the process previously described in E18-E21, except that no metal-ligand complex was included in the heterogeneous procatalyst.
[0132] Evaluation and comparison of ethylene-based polymers of Examples E18-E23 and Comparative Examples CE7-CE9. The ethylene-based polymers collected from the copolymerizations of E18-E23 and CE7-CE9 were evaluated for Mw, C8 wt%, and HDF according to the test methods described herein, and the results are provided below in Table 6. Δ(Mw), Δ(C8 wt%), and Δ(HDF) for E18, E19, E20, E21, E22, E23, CE7, and CE8 in Table 6 were calculated as the change from CE9. [Table 7]
[0133] Comparison of ethylene-based polymers of CE7, CE8, and CE9 demonstrates that producing an ethylene-based polymer in the presence of preformed heterogeneous procatalysts with heat-treated MgCl2 (CE7 and CE8) can increase the Mw, increase the HDF, and decrease the C8 wt% of the ethylene-based polymer compared to an ethylene-based polymer prepared with a comparative preformed procatalyst without heat-treated MgCl2 (CE9).
[0134] Comparison of the ethylene-based polymers of E22 and E23 with the ethylene-based polymer of CE9 demonstrates that the inclusion of a metal-ligand complex as a donor compound in the heterogeneous procatalyst (E22 and E23) can increase the Mw, increase the HDF wt%, and decrease the C8 wt% of the ethylene-based polymer compared to an ethylene-based polymer prepared with a comparative procatalyst (CE9) that does not include the metal-ligand complex as a donor compound under the same reactor process conditions. The increase in Mw and HDF wt%, as well as the decrease in C8 wt%, of the ethylene-based polymer can be achieved by including a metal-ligand complex as a donor compound in the heterogeneous procatalyst without heat treating the MgCl2 component.
[0135] Ti(O) as a metal-ligand complex donor compound i The heterogeneous procatalyst (E18) with heat-treated MgCl2 in combination with (Ti(OPr)4 produced ethylene-based polymers in CE9, as well as E22 (heat-treated MgCl2-free, (Ti(OPr)4). iComparison of ethylene-based polymers of E18, E22, CE7, and CE9 demonstrates that the inclusion of both heat-treated MgCl2 and a metal-ligand complex in the heterogeneous procatalyst produces ethylene-based polymers with higher Mw, higher HDF wt%, and reduced C8 wt%, compared to ethylene-based polymers of CE10 (thermally treated MgCl2 without a metal-ligand complex donor compound), CE20 (thermally treated MgCl2 without a metal-ligand complex donor compound), and CE3 (thermally treated MgCl2 without a metal-ligand complex donor compound). Thus, the inclusion of both heat-treated MgCl2 and a metal-ligand complex in the heterogeneous procatalyst can provide a higher increased Mw and HDF wt%, and a greater reduced C8 wt%, of the ethylene-based polymer compared to the inclusion of either heat-treated MgCl2, or a metal-ligand complex, but not both, in the heterogeneous procatalyst. In E20, ethylene-based polymers were produced in the presence of a heterogeneous catalyst based on the preformed procatalyst of Example E, which had a lower content of EADC and Ti (40 / 6.8 / 1.7 MgCl2 / EADC / Ti) compared to the preformed procatalyst of Example D used in E18 (40 / 12 / 3 MgCl2 / EADC / Ti). The increase in Mw and HDF of the ethylene-based polymers, as well as the decrease in C8 wt%, are due to the fact that the heterogeneous procatalyst incorporates lower amounts of EADC (chlorinating agent) and Ti (titanium species), even when Ti(O i A comparison of ethylene-based polymers E20, E22, CE8, and CE9 demonstrates that this can be achieved by the inclusion of heat-treated MgCl2 in combination with the Pr)4 metal-ligand complex.
[0136] VO(O) as a metal-ligand complex donor compound n The heterogeneous procatalyst (E19) containing heat-treated MgCl2 in combination with (VO(O)Bu)3 produced ethylene-based polymers in CE9, as well as E23 (heat-treated MgCl2-free, (VO(O)Bu). nComparison of ethylene-based polymers E19, E23, CE7, and CE9 demonstrates that E21 produces ethylene-based polymers with higher Mw, higher HDF wt%, and reduced C8 wt% compared to ethylene-based polymers of VO(O)3, VO(Bu)3 metal-ligand complex), and CE7 (thermally treated MgCl2 without metal-ligand complex donor compound). In E21, an ethylene-based polymer was produced in the presence of a heterogeneous catalyst including the preformed procatalyst of Example E, which had a reduced molar ratio of EADC and Ti (MgCl2 / EADC / Ti of 40 / 6.8 / 1.7) compared to the preformed procatalyst of Example D used in E19 (MgCl2 / EADC / Ti of 40 / 12 / 3). The increase in Mw and HDF of the ethylene-based polymer, as well as the decrease in C8 wt%, are due to the fact that the heterogeneous procatalyst incorporates lower amounts of EADC and Ti. n A comparison of ethylene-based polymers E21, E23, CE8, and CE9 demonstrates that this can be achieved by the inclusion of heat-treated MgCl2 in combination with the Bu)3 metal-ligand complex.
[0137] In a first aspect of the present disclosure, the heterogeneous procatalyst comprises a titanium species and at least 100m 2 The method may include a preformed MgCl2 support having a specific surface area of 100 nm / g, a chlorinating agent, and a metal-ligand complex. The chlorinating agent has the structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. The metal-ligand complex has the structural formula (L): n M(Y) m (XR 2 ) b where M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0138] A second embodiment of the present disclosure may include the following embodiment, wherein the chlorinating agent is selected from ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum sesquichloride, isobutylaluminum dichloride, diisobutylaluminum chloride, and combinations thereof.
[0139] A third aspect of the present disclosure is a method for preparing a titanium species comprising the steps of: 4ーc (OR 3 ) c or TiCl 3ーd (OR 3 ) d where R 3 But, (C1-C 20 ) hydrocarbyl, c is 0, 1, 2, 3, or 4, and d is 0, 1, 2, or 3.
[0140] A fourth aspect of the present disclosure relates to the ratio of the total amount of chlorine in the chlorinating agent to the OR in the heterogeneous procatalyst. 3 and XR 2 The molar ratio of the total amount of the above may be 0.33 to 1.45.
[0141] A fifth aspect of the present disclosure may include any of the first through fourth aspects, wherein the titanium species is selected from TiCl4, TiCl3, TiCl2(OC2H5)2, TiCl2(O-i-C3H7)2, TiCl2(O-n-C4H9)2, TiCl2(O-i-C4H9)2, TiCl(O-i-C3H7)3, TiCl(O-n-C4H9)3, TiCl(O-i-C4H9)3, Ti(OC2H5)4, Ti(O-i-C3H7)4, Ti(O-n-C4H9)4, Ti(O-i-C4H9)4, and Ti(OCH2CH(C2H5)(C4H9))4.
[0142] A sixth aspect of the present disclosure may include any of the first through fifth aspects, wherein the MgCl support is a reaction product of a solution of an alkylmagnesium compound in a hydrocarbon diluent and a chloride source without isolating the hydrocarbon diluent.
[0143] A seventh aspect of the present disclosure may include the sixth aspect, wherein the metal-ligand complex is at least partially soluble in the hydrocarbon diluent of the MgCl2 support.
[0144] An eighth embodiment of the present disclosure can include any of the first through seventh embodiments, wherein the molar ratio of chlorinating agent to MgCl2 in the heterogeneous procatalyst is from 0.05:1 to 2:1.
[0145] A ninth aspect of the present disclosure can include any of the first to eighth aspects, wherein the molar ratio of titanium species to MgCl2 in the heterogeneous procatalyst is from 0.005:1 to 0.25:1.
[0146] In a tenth aspect of the present disclosure, the heterogeneous procatalyst can include a preformed heterogeneous procatalyst including a titanium species and a MgCl2 support. The heterogeneous procatalyst can be represented by structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0147] An eleventh aspect of the present disclosure is a metal-ligand complex having the structural formula M(OR 2 ) e wherein e is 2, 3, 4, 5, or 6.
[0148] A twelfth aspect of the present disclosure is a metal-ligand complex having the structural formula M(=O)(OR 2 ) f wherein f is 1, 2, 3, or 4.
[0149] A thirteenth aspect of the present disclosure may include any of the first to twelfth aspects, in which M is a transition metal cation.
[0150] A fourteenth aspect of the present disclosure can include any of the first through twelfth aspects, in which M is a main group metal cation.
[0151] A fifteenth aspect of the present disclosure may include any of the first to twelfth aspects, wherein M is vanadium, titanium, scandium, zirconium, niobium, magnesium, or calcium.
[0152] A sixteenth aspect of the present disclosure can include any of the first through thirteenth aspects, wherein the metal-ligand complex includes at least one of vanadium(V) oxytripropoxide, vanadium(V) oxytributoxide, vanadium(V) oxytriisopropoxide, titanium(IV) isopropoxide, titanium(IV) ethoxide, or a combination thereof.
[0153] A seventeenth aspect of the present disclosure can include any of the first through sixteenth aspects, where the procatalyst further includes an additional transition metal compound.
[0154] An eighteenth aspect of the present disclosure can include the seventeenth aspect, wherein the additional transition metal compound can be independently selected from zirconium, hafnium, vanadium, and chromium.
[0155] A nineteenth embodiment of the present disclosure can include any of the first through eighteenth embodiments, where the heterogeneous procatalyst can be prepared by a process including heat treating magnesium chloride at a temperature greater than 100° C. and a treatment time of at least 30 minutes to form a magnesium chloride component, and then contacting the magnesium chloride component with a titanium species.
[0156] A twentieth aspect of the present disclosure relates to a catalyst system for olefin polymerization, which may include any of the first to nineteenth aspects, and may include a heterogeneous procatalyst according to any of the first to nineteenth aspects, and a cocatalyst comprising an organoaluminum compound.
[0157] In a twenty-first aspect of the present disclosure, a catalyst system for olefin polymerization can include a preformed heterogeneous procatalyst comprising a titanium species and a MgCl2 support. The catalyst system can be represented by structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge. The catalyst system may further comprise a cocatalyst comprising an organoaluminum compound.
[0158] A twenty-second embodiment of the present disclosure may include the twenty-first embodiment, wherein the co-catalyst is selected from an alkylaluminum, a haloalkylaluminum, an alkylaluminum halide, and combinations thereof.
[0159] A twenty-third aspect of the present disclosure may include any of the twentieth to twenty-second aspects, wherein the polymerization process may include contacting ethylene and optionally one or more α-olefin comonomers with a catalyst system according to any one of the twentieth to twenty-second aspects.
[0160] A twenty-fourth aspect of the present disclosure may include the twenty-third aspect, wherein the polymerization process is a solution polymerization process.
[0161] In a twenty-fifth aspect of the present disclosure, a process for preparing a heterogeneous procatalyst can include contacting a magnesium chloride component with a chlorinating agent, a titanium species, and a metal-ligand complex. The magnesium chloride component is at least 100 m 2 The chlorinating agent may be a preformed MgCl2 support having a specific surface area of 1000 nm / g. The chlorinating agent may have the structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3, and y is 1, 2, 3, or 4. The metal-ligand complex has the structural formula (L): n M(Y) m (XR 2 ) bwhere M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0162] In a twenty-sixth aspect of the present disclosure, a process for preparing a heterogeneous procatalyst can include contacting components (1) and (2) without further chlorination. Component (1) can be a preformed heterogeneous procatalyst comprising a titanium species and a MgCl2 support. Component (2) can be a compound represented by structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation, each L is a neutral ligand or (=O), and each Y is a halide or (C1-C 20 ) alkyl, and each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) heterohydrocarbyl, n is 0, 1, or 2, m is 0, 1, 2, 3, or 4, and b is 1, 2, 3, 4, 5, or 6, and the metal-ligand complex is overall neutral in charge.
[0163] A twenty-seventh aspect of the present disclosure may include either the twenty-fifth or twenty-sixth aspects, wherein the metal-ligand complex is in a hydrocarbon solution.
[0164] A twenty-eighth aspect of the present disclosure may include any of the twenty-fifth to twenty-second aspects, further including heat treating the magnesium chloride at a temperature above 100° C. for a treatment time of at least 30 minutes.
[0165] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Accordingly, it is intended that the present specification cover modifications and variations of the various embodiments described herein, provided that such modifications and variations come within the scope of the appended claims and their equivalents. The present invention includes the following aspects. Section 1. 1. A heterogeneous procatalyst comprising: Titanium species, At least 100m 2 a preformed MgCl2 support having a specific surface area of 1000 nm / g; Structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y A chlorinating agent having the formula: R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3; a chlorinating agent, wherein y is 1, 2, 3, or 4; Structural formula (L) n M(Y) m (XR 2 ) b A metal-ligand complex having the formula: M is a metal cation; each L is a neutral ligand or (=O); Each Y is a halide or (C1-C 20 ) alkyl, Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20) hydrocarbyl or (C1-C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; A heterogeneous procatalyst, wherein the metal-ligand complex is overall charge neutral. Section 2. Item 2. The heterogeneous procatalyst of item 1, wherein the chlorinating agent is selected from ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum sesquichloride, isobutylaluminum dichloride, diisobutylaluminum chloride, and combinations thereof. Section 3. The titanium species is TiCl 4-c (OR 3 ) c or TiCl 3-d (OR 3 ) d where R 3 But, (C1-C 20 3. The heterogeneous procatalyst of claim 1 or 2, wherein c is 0, 1, 2, 3, or 4, and d is 0, 1, 2, or 3. Section 4. Total amount of chlorine in the chlorinating agent vs. OR in the heterogeneous procatalyst 3 and XR 2 Item 4. The heterogeneous procatalyst according to item 3, wherein the molar ratio of the total amount of is 0.33 to 1.45. Section 5. 5. The heterogeneous procatalyst according to any one of items 1 to 4, wherein the titanium species is selected from TiCl, TiCl, TiCl(OCH), TiCl(Oi-CH), TiCl(On-CH), TiCl(Oi-CH), TiCl(On-CH), TiCl(Oi-CH), Ti(OCH), Ti(Oi-CH), Ti(On-CH), Ti(Oi-CH), Ti(On-CH), Ti(Oi-CH), and Ti(OCHCH(CH)(CH)). Section 6. 6. The heterogeneous procatalyst according to any one of items 1 to 5, wherein the MgCl2 support is the reaction product of a solution of an alkyl magnesium compound in a hydrocarbon diluent and a chloride source, and the hydrocarbon diluent is not separate from the MgCl2 support. Section 7. 7. The heterogeneous procatalyst according to any one of items 1 to 6, wherein the molar ratio of the chlorinating agent to the MgCl2 support in the heterogeneous procatalyst is 0.05:1 to 2:1. Section 8. 8. The heterogeneous procatalyst according to any one of items 1 to 7, wherein the molar ratio of the titanium species to the MgCl2 support in the heterogeneous procatalyst is 0.005:1 to 0.25:1. Section 9. 1. A heterogeneous procatalyst comprising: A preformed heterogeneous procatalyst comprising: Titanium species, and a preformed heterogeneous procatalyst comprising a MgCl2 support; Structural formula (L) n M(Y) m (XR 2 ) b A metal-ligand complex having the formula: M is a metal cation; each L is a neutral ligand or (=O); Each Y is a halide or (C1-C 20 ) alkyl, Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; A heterogeneous procatalyst, wherein the metal-ligand complex is overall charge neutral. Section 10. The metal-ligand complex has the structural formula M(OR 2 ) e where e is 2, 3, 4, 5, or 6, or a metal alkoxide having the structural formula M(=O)(OR 2 ) f (wherein f is 1, 2, 3, or 4). Section 11. 11. The heterogeneous procatalyst according to any one of items 1 to 10, wherein M is selected from at least one of a vanadium cation, a titanium cation, a scandium cation, a zirconium cation, a niobium cation, a magnesium cation, or a calcium cation. Section 12. 12. The heterogeneous procatalyst of any one of paragraphs 1 to 11, wherein the metal-ligand complex comprises at least one of vanadium(V) oxytripropoxide, vanadium(V) oxytributoxide, vanadium(V) oxytriisopropoxide, titanium(IV) isopropoxide, titanium(IV) ethoxide, or a combination thereof. Section 13. 13. The heterogeneous procatalyst according to any one of items 1 to 12, prepared by a process comprising heat treating magnesium chloride at a temperature above 100° C. and for a treatment time of at least 30 minutes to form the magnesium chloride component, and then contacting the magnesium chloride component with the titanium species. Section 14. 1. A catalyst system for the polymerization of olefins, comprising: A heterogeneous procatalyst according to any one of items 1 to 13, and a cocatalyst comprising an organoaluminum compound. Section 15. 15. The catalyst system of claim 14, wherein the cocatalyst is selected from alkylaluminum, haloalkylaluminum, alkylaluminum halide, and combinations thereof. Section 16. 16. A polymerization process comprising contacting ethylene and optionally one or more α-olefin comonomers with the catalyst system of claim 14 or 15. Section 17. Item 17. The polymerization process according to item 16, wherein the polymerization process is a solution polymerization process. Section 18. A process for preparing a heterogeneous procatalyst, comprising contacting a magnesium chloride component with a chlorinating agent, a titanium species, and a metal-ligand complex; The magnesium chloride component is at least 100m 2 is a preformed MgCl2 support having a specific surface area of 1 / g; The chlorinating agent has the structural formula Al(Cl) x (R 1 ) 3-x or Si(Cl) y (R 1 ) 4-y wherein R 1 But, (C1-C 30 ) hydrocarbyl, x is 1, 2, or 3; y is 1, 2, 3, or 4; The metal-ligand complex has the structural formula (L): n M(Y) m (XR 2 ) b wherein M is a metal cation; each L is a neutral ligand or (=O); Each Y is a halide or (C1-C 20 ) alkyl, Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; The process wherein said metal-ligand complex is overall charge neutral. Section 19. 1. A process for preparing a heterogeneous procatalyst, comprising contacting, without further chlorination, components (1) and (2): Component (1) is a preformed heterogeneous procatalyst, Titanium species, MgCl2 support; and a preformed heterogeneous procatalyst comprising: Component (2) has the structural formula (L) n M(Y) m (XR 2 ) b A metal-ligand complex having the formula: M is a metal cation; each L is a neutral ligand or (=O); Each Y is a halide or (C1-C 20 ) alkyl, Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, and R 2 But, (C1-C 20 ) hydrocarbyl or (C1-C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; The process wherein said metal-ligand complex is overall charge neutral. Section 20. 20. The process of claim 18 or 19, further comprising heat treating the magnesium chloride at a temperature above 100° C. for a treatment time of at least 30 minutes.
Claims
1. 1. A heterogeneous procatalyst comprising: Structural formula TiCl 4-c (OR 3 ) c or TiCl 3-d (OR 3 ) d A titanium species having the formula: R 3 However, (C 1 -C 20 ) hydrocarbyl, c is 0, 1, 2, 3, or 4; a titanium species, wherein d is 0, 1, 2, or 3; At least 100m 2 Preformed MgCl having a specific surface area of 1.0 μm / g 2 A support; Structural formula Al(Cl) x (R 1 ) 3-x Or Si(Cl) y (R 1 ) 4-y A chlorinating agent having the formula: R 1 However, (C 1 -C 30 ) hydrocarbyl, x is 1, 2, or 3; a chlorinating agent, wherein y is 1, 2, 3, or 4; Structural formula (L) n M (Y) m (XR 2 ) b A metal-ligand complex having the formula: M is a titanium cation or a vanadium cation; each L is a neutral ligand or (=O); Each Y is a halide or (C 1 -C 20 ) alkyl; Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, R 2 However, (C 1 -C 20 ) hydrocarbyl or (C 1 -C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; the metal-ligand complex is overall charge neutral; The total amount of chlorine in the chlorinating agent versus the OR in the heterogeneous procatalyst 3 and XR 2 is from 0.33 to 1.
45.
2. 2. The heterogeneous procatalyst of claim 1, wherein the chlorinating agent is selected from ethylaluminum dichloride, diethylaluminum chloride, isobutylaluminum dichloride, diisobutylaluminum chloride, and combinations thereof.
3. The titanium species is TiCl 4 , TiCl 3 , TiCl 2 (OC 2 H 5 ) 2 , TiCl 2 (O-i-C 3 H 7 ) 2 , TiCl 2 (O-n-C 4 H 9 ) 2 , TiCl 2 (O-i-C 4 H 9 ) 2 , TiCl(O-i-C 3 H 7 ) 3 , TiCl(O-n-C 4 H 9 ) 3 , TiCl(O-i-C 4 H 9 ) 3 , Ti(OC 2 H 5 ) 4 , Ti(O-i-C 3 H 7 ) 4 , Ti(O-n-C 4 H 9 ) 4 , Ti(O-i-C 4 H 9 ) 4 , and Ti(OCH 2 CH (C 2 H 5 ) (C 4 H 9 )) 4 3. The heterogeneous procatalyst of claim 1 or 2, selected from:
4. The MgCl 2 The support is the reaction product of a solution of an alkyl magnesium compound in a hydrocarbon diluent and a chloride source, the hydrocarbon diluent being the MgCl 2 The heterogeneous procatalyst of any one of claims 1 to 3, which is not separated from a support.
5. The chlorinating agent versus MgCl in the heterogeneous procatalyst 2 The heterogeneous procatalyst of any one of claims 1 to 4, wherein the molar ratio of the support is from 0.05:1 to 2:
1.
6. The titanium species versus MgCl in the heterogeneous procatalyst 2 The heterogeneous procatalyst of any one of claims 1 to 5, wherein the molar ratio of the support is from 0.005:1 to 0.25:
1.
7. The metal-ligand complex has the structure M(OR 2 ) e where e is 2, 3, 4, 5, or 6, or a metal alkoxide having the structure M(═O)(OR 2 ) f The heterogeneous procatalyst of any one of claims 1 to 6, which is a metal oxyalkoxide having the formula: wherein f is 1, 2, 3, or 4.
8. 7. The heterogeneous procatalyst of any of claims 1 to 6, wherein the metal-ligand complex comprises at least one of vanadium(V) oxytripropoxide, vanadium(V) oxytributoxide, vanadium(V) oxytriisopropoxide, titanium(IV) isopropoxide, titanium(IV) ethoxide, or combinations thereof.
9. Magnesium chloride is heat treated at a temperature above 100° C. and for a treatment time of at least 30 minutes to obtain the MgCl 2 The support is then prepared and the MgCl 2 The heterogeneous procatalyst of any of claims 1 to 8, prepared by a process comprising contacting a support with said titanium species.
10. 1. A catalyst system for the polymerization of olefins, comprising: A heterogeneous procatalyst according to any one of claims 1 to 9; and a cocatalyst comprising an organoaluminum compound.
11. 11. The catalyst system of claim 10, wherein the cocatalyst is selected from alkylaluminums, haloalkylaluminums, alkylaluminum halides, and combinations thereof.
12. A polymerization process comprising contacting ethylene and optionally one or more α-olefin comonomers with the catalyst system of claim 10 or 11.
13. 13. The polymerization process of claim 12, wherein the polymerization process is a solution polymerization process.
14. A process for preparing a heterogeneous procatalyst, comprising contacting a magnesium chloride component with a chlorinating agent, a titanium species, and a metal-ligand complex; The titanium species has the structural formula TiCl 4-c (OR 3 ) c or TiCl 3-d (OR 3 ) d wherein R 3 However, (C 1 -C 20 ) hydrocarbyl, c is 0, 1, 2, 3, or 4; d is 0, 1, 2, or 3; The magnesium chloride component is at least 100 m 2 Preformed MgCl having a specific surface area of 1.0 μm / g 2 A support, The chlorinating agent has the structural formula Al(Cl) x (R 1 ) 3-x Or Si(Cl) y (R 1 ) 4-y wherein R 1 However, (C 1 -C 30 ) hydrocarbyl, x is 1, 2, or 3; y is 1, 2, 3, or 4; The metal-ligand complex has the structural formula (L): n M (Y) m (XR 2 ) b wherein M is a titanium cation or a vanadium cation; each L is a neutral ligand or (=O); Each Y is a halide or (C 1 -C 20 ) alkyl; Each XR 2 is an anionic ligand, X is a heteroatom or a heteroatom-containing functional group, R 2 However, (C 1 -C 20 ) hydrocarbyl or (C 1 -C 20 ) an anionic ligand which is a heterohydrocarbyl; n is 0, 1 or 2; m is 0, 1, 2, 3, or 4; b is 1, 2, 3, 4, 5, or 6; the metal-ligand complex is overall charge neutral; The total amount of chlorine in the chlorinating agent versus the OR in the heterogeneous procatalyst 3 and XR 2 is from 0.33 to 1.
45.
15. 15. The process of claim 14, further comprising heat treating the magnesium chloride component at a temperature above 100°C for a treatment time of at least 30 minutes.
Citation Information
Patent Citations
Polymerization of olefins
GB1292853A
Carried catalyst
JP1992224807A
Method of making a Ziegler-Natta olefin polymerization catalyst
US5747407A
Magnesium halide-supported titanium (PRO) catalysts
WO2018063899A1